Recognizing topological attributes and spatiotemporal patterns in spotted seals (Phoca largha) trophic networks based on eDNA metabarcoding - Yan Xu; Fei Huang; Mingliang Zhou; Rui Gu; Jie Zhu; Qiangqiang Rong; Yanpeng Cai (Frontiers in Marine Science, 2023)
Spotted seals, a protected species, face multifaceted threats to their habitat, which in turn impact the closely associated trophic networks. These threats will lead to irreversible structural variations within the ecosystem. Therefore, investigating the topological variability of trophic networks in spotted seals is important. Applying environmental DNA methods, field sample collection was conducted in 2021 during both the sea fishing moratorium period and the fishing period to decode fish diversity. Assessing the current status of fish resources by using the multivariate statistics approach. Applying dietary information establishes the spotted seals’ trophic network. Selecting 12 network indexes to analyze the spatiotemporal patterns of network topological attributes. As a result, about 51 families, and 76 genera species were identified. During the sea fishing moratorium and the fishing period, there are 12 and 18 different food resources available for spotted seals, respectively. The diversity index revealed that the FP had greater species richness and diversity than the SP. Comparatively, the Fishing period exhibited higher species richness and biodiversity, likely influenced by habitat heterogeneity and anthropogenic activities. Additionally, the topological features of networks reflected the high clustering coefficients (CC=0.35) and the proportion of omnivorous species (O≈60%), indicating that the network structure in this region tends to form higher trophic-level clustering patterns, which facilitate the formation of weaker interactions between clusters, enhancing the robustness of the network. The higher connectivity complexity index during the fishing period (SC=12.3) supported that the spotted seal’s trophic network was relatively more stable in this period. Thus, during the fishing period, it is crucial to pay more attention to the intensity of human fishing on mid-to-high trophic-level omnivorous fish resources to ensure the sustainability of these potential food resources for spotted seals. This comprehensive study achieved three key objectives: (a) utilizing eDNA to characterize fish diversity during distinct periods, (b) establishing trophic networks of spotted seals, and (c) discerning topological attributes and spatiotemporal patterns within the ecological network. Overall, this study can provide technical and data support for integrated ecological network management and propose suggestions for protecting and recovering spotted seals.

A high-resolution α-glucosidase inhibition profiling for targeted identification of natural antidiabetic products from Lycopodiella cernua (L.) Pic. Serm and their inhibitory mechanism study - Bing-Rui Liu; Xu-Liu Shi; Jian-Kun Yan; Rui Zhao (Natural Product Research, 2023)

Effect of vane angle on turbulence–chemistry interactions, temperature, flow field, burnout, and NOx emissions in swirling flames fueled by semicoke mixtures - Liutao Sun; Shengyu Kuang; Weilin Li; Jingjie Wang; Yanhui Xu; Lingkun Zhu; Hong Tian; Xinzhuo Li; Dengke Wang; Rui Sun (Environmental Science and Pollution Research, 2023)

First report of Fusarium sacchari causing root rot of tobacco (Nicotiana tabacum L.) in China - Rui Qiu; Caihong Li; Xiaojie Li; Yingying Zhang; Chang Liu; Chenjun Li; Yuguo Chen; Jingke Bai; Min Xu; Ruifang Song; Shujun Li (Crop Protection, 2023)

Increased m6A-RNA methylation and demethylase FTO suppression is associated with silica-induced pulmonary inflammation and fibrosis - Yunyi Xu; Liqun Wang; Rui Qian; Manyu Zhao; Xuxi Chen; Donglei Sun; Ye Wang; Weibo Cheng; Yiping Chen; Qiurong He; Yi Dai; Yuqin Yao (Toxicology, 2023)

Increasing sensitivity of dryland water use efficiency to soil water content due to rising atmospheric CO2 - Rui Kong; Zengxin Zhang; Zejiang Yu; Richao Huang; Ying Zhang; Xi Chen; Chong-Yu Xu (Science of The Total Environment, 2023)

Granulation of partial denitrification sludge: Advances in mechanism understanding, technologies development and perspectives - Duanyuan Xu; Shenbin Cao; Maxence Berry; Rui Du; Yongzhen Peng (Science of The Total Environment, 2023)

Nano- and micro-plastic transport in soil and groundwater environments: Sources, behaviors, theories, and models - Jun Xu; Rui Zuo; Jinhua Shang; Guanlan Wu; Yanan Dong; Shida Zheng; Zuorong Xu; Jingchao Liu; Yunxiang Xu; Ziyi Wu; Chenxi Huang (Science of The Total Environment, 2023)

Alkali-thermal activated persulfate treatment of tetrabromobisphenol A in soil: Parameter optimization, mechanism, degradation pathway and toxicity evaluation - Yushuang Chen; Rui Shi; Yafei Hu; Wenlai Xu; Neng-min Zhu; Haijiao Xie (Science of The Total Environment, 2023)

Moderate selenium alleviates the pulmonary function impairment induced by cadmium and lead in adults: A population-based study - Heze Fan; Ying Xiong; Yuzhi Huang; Lijun Wang; Chenbo Xu; Wenyuan Li; Xueying Feng; Yuxuan Yang; Rui Hua; Zihao Wang; Zuyi Yuan; Juan Zhou (Science of The Total Environment, 2023)

Fabrication of high permeability and antifouling composite membrane loaded with Fe3O4 nanoparticles via a magnetic field induced phase separation - Meng Zhang; Shu Jiang; Xishou Guo; Xiaobin Tang; Langming Bai; Jinlong Wang; Han Zhang; Daliang Xu; Rui Wu; Luming Liu; Heng Liang (Journal of Water Process Engineering, 2023)

Application of alkaline sludge based LDHs in Cd and Cu polluted wastewater remediation: Process and mechanism - Qingsheng Xu; Zhengbo Yue; Rui Deng; Xinquan Wang; Xiao He; Xin Chuai; Shaoping Wang; Jin Wang (Journal of Water Process Engineering, 2023)

PbBPC4 involved in a xylem-deficient dwarf phenotype in pear by directly regulating the expression of PbXND1 - Di Wang; Bingqing Qie; Azheng Wang; Minmin Wang; Pingyuan Dai; Lijuan Xiao; Rui Zhai; Chengquan Yang; Zhigang Wang; Lingfei Xu (Journal of Plant Physiology, 2023)

Climate resilience assessment of sustainability at national level: A case study of sub-Saharan Africa - Meiyu Xiong; Rui Zhao; Xia Li; Ying Wang; Zhenci Xu; Fengting Li (Journal of Cleaner Production, 2023)

Synergistic effect triggered by Fe2O3 and oxygen-induced hydroxyl radical enhances formation of amino-phenolic humic-like substance - Yingchao Zhang; Zhitao Bi; Wenxin Tian; Zhenyu Ge; Yang Xu; Rui Xu; Hongqiong Zhang; Shoufeng Tang (Journal of Environmental Management, 2023)

Performance optimization and nitrogen removal mechanism of up-flow partial denitrification/anammox process - Youqi Tao; Rui Shi; Linjing Li; Suhui Xia; Jianyong Ning; Wenlai Xu (Journal of Environmental Management, 2023)

pH-responsive ZIF-8 film-coated mesoporous silica nanoparticles for clean, targeted delivery of fungicide and environmental hazard reduction - Yingjian Ma; Yinmin Wang; Rui Zhao; Zhijie Wang; Shuang Li; Meng Yu; Sen Pang; Xinyu Guo; Yong Xu; Xuemin Wu (Journal of Environmental Chemical Engineering, 2023)

Carbon and nitrogen transformation mechanism and functional microorganisms of sheep manure composting on the Qinghai-Tibet Plateau under different moisture content - Rui Cai; Sasa Zuo; Xiaohui Cao; Chuncheng Xu (Journal of Environmental Chemical Engineering, 2023)

Low-carbon economic analysis of a virtual power plant with wind and solar power considering the integrated flexible operation mode of a carbon capture thermoelectric unit - Chunming Zhu; Gang Bao; Rui Xu; Zhenyan Song; Yikai Liu (International Journal of Greenhouse Gas Control, 2023)

Experimental research on the venting characteristics of methane and coal dust two-phase system mixture explosions - Xingyan Cao; Rui Huang; Yawei Lu; Zhirong Wang; Longtao Fan; Yangqing Zhou; Jianjun Xu (Fuel, 2023)

Obese people are more likely to exhibit unhealthy food decisions when sated - Zhongquan Du; Jiaai Huang; Rui Xia; Pavel N. Ermakov; Xia Xu (Food Quality and Preference, 2023)

Cyanidin-3-O-glucoside from blueberry anthocyanin extracts protects ARPE-19 cells against high glucose damage via REDD1/GSK3β pathway - Rui Li; Zhan Ye; Yong-jiang Xu; Yuanfa Liu (Food Bioscience, 2023)

Micro-algal astaxanthin ameliorates polystyrene microplastics-triggered necroptosis and inflammation by mediating mitochondrial Ca2+ homeostasis in carp’s head kidney lymphocytes (Cyprinus carpio L.) - Lei Diao; Meiqi Ding; Hongzhen Sun; Yawei Xu; Rui Yin; Huijie Chen (Fish & Shellfish Immunology, 2023)

An investigation into the modal effect mechanism of multi-mode coupled flutter with modality-driven method - Jinbo Zhu; Yongxin Yang; Haojun Xu; Jinjie Zhang; Rushen Su; Yaojun Ge; Rui Zhou; Yizhe Lan (Engineering Structures, 2023)

TUMME 2023: Tsinghua University Minnesota Master Equation program. New version announcement - Rui Ming Zhang; Xuefei Xu; Donald G. Truhlar (Computer Physics Communications, 2023)

Conversion of highly polymerized lignin into monophenolic products via pyrolysis: A comparative study of acidic and alkaline depolymerization pretreatments using deep eutectic solvents - Xin Yue; Jinxin Lin; Terhi Suopajärvi; Otto Mankinen; Atte Mikkelson; Rui Liu; Harri Huttunen; Liheng Chen; Chunlin Xu; Ville-Veikko Telkki; Shirong Sun; Henrikki Liimatainen (Chemical Engineering Journal, 2023)

Oxalic acid-enhanced sulfamethoxazole degradation by V2O3/percarbonate process: Insights into the reactive oxygen species generation and conversion - Rui Liu; Mu-cheng Xu; Jin-yan Yang (Chemical Engineering Journal, 2023)

Promoting reversibility of layered potassium cathode through interstitial doping - Xuan Xu; Xun-Lu Li; Muhammad Mominur Rahman; Jian Bao; Rui-Jie Luo; Cui Ma; Chong-Yu Du; Jie Zeng; Zhe Mei; Zhe Qian; Enyuan Hu; Yong-Ning Zhou (Chemical Engineering Journal, 2023)

Chemical constituents from Mytilaria laosensis Lec. leaves and branches - Xiaofang Ye; Yingxin Liang; Boxuan Liao; Chen Ni; Huaqiang Lu; Rui He; Cuixian Zhang; Hui Xu; Jinchang Yang (Biochemical Systematics and Ecology, 2023)

Research Progress on TRPA1 in Diseases - Jiajing Li; Hongfei Zhang; Qian Du; Junyu Gu; Jiangbo Wu; Qi Liu; Zhuo Li; Ting Zhang; Jingyu Xu; Rui Xie (The Journal of Membrane Biology, 2023)
For a long time, the physiological activity of TRP ion channels and the response to various stimuli have been the focus of attention, and the physiological functions mediated by ion channels have subtle links with the occurrence of various diseases. Our group has been engaged in the study of ion channels. In recent years, the report rate of TRPA1 , the only member of the TRPA subfamily in the newly described TRP channel, has been very high. TRPA1 channels are not only abundantly expressed in peptidergic nociceptors but are also found in many nonneuronal cell types and tissues, and through the regulation of Ca 2+ influx, various neuropeptides and signaling pathways are involved in the regulation of nerves, respiration, circulation, and various diseases and inflammation throughout the body. In this review, we mainly summarize the effects of TRPA1 on various systems in the body, which not only allows us to have a more systematic and comprehensive understanding of TRPA1 but also facilitates more in-depth research on it in the future. Graphical Abstract

Shared and Distinct Topographic Alterations of Alpha-Range Resting EEG Activity in Schizophrenia, Bipolar Disorder, and Depression - Rui Xue; Xiaojing Li; Jianning Chen; Sugai Liang; Hua Yu; Yamin Zhang; Wei Wei; Yan Xu; Wei Deng; Wanjun Guo; Tao Li (Neuroscience Bulletin, 2023)

The Role of Cystathionine-β-Synthase, H2S, and miRNA-377 in Hypoxic-Ischemic Encephalopathy: Insights from Human and Animal Studies - Chun-Yang Liu; Hisham Al-Ward; Ning Liu; Francine Ngaffo Mekontso; Wei Chen; Wenxia Gao; Chunxue Zhang; Abduh Murshed; Zi-Rui Yu; Orion Fan; Yi Eve Sun; Hui Xu (Journal of Molecular Neuroscience, 2023)

Serum HBV RNA levels among untreated adults with chronic hepatitis B in distinct immune phases and liver histopathology statuses - Qin Xu; Hai Ding; Tao Bai; Rui Huang; Jian Wang; Jun Zhang; Hewei Luan; Jun Wang; Yue Yang; Yuxin Chen (Journal of Molecular Histology, 2023)

Three-dimensional visualization of the lymphatic, vascular and neural network in rat lung by confocal microscopy - Shitong Zhao; Jingjing Cui; Yuqing Wang; Dongsheng Xu; Yuxin Su; Jie Ma; Xuefeng Gong; Wanzhu Bai; Jia Wang; Rui Cao (Journal of Molecular Histology, 2023)

Mitochondrial dysfunction: a new molecular mechanism of intervertebral disc degeneration - Chao Song; Yulin Xu; Qinghua Peng; Rui Chen; Daqian Zhou; Kang Cheng; Weiye Cai; Tao Liu; Chenyi Huang; Zhijiang Fu; Cong Wei; Zongchao Liu (Inflammation Research, 2023)

Genome resequencing reveals the population structure and genetic diversity of almond in Xinjiang, China - Pengyu Wu; Dong Li; Rui Zhuang; Hao Zuo; Zhiyong Pan; Bo Yang; Chongzhi Xu (Genetic Resources and Crop Evolution, 2023)

Dietary supplementation of pyridoxine can enhance the growth performance and improve the protein, lipid utilization efficiency of mandarin fish (Siniperca chuatsi) - Rui-Peng Xie; Xu-Fang Liang; Di Peng; Qi-Wei Zhang; Dong-Liang Wu; Jun-Liang Chen; Ming Zeng (Fish Physiology and Biochemistry, 2023)

Soil microbial communities as potential regulators of N2O sources in highly acidic soils - Junhui Yin; Huaihai Chen; Pengpeng Duan; Kun Zhu; Naihui Li; Yan Ma; Yumeng Xu; Jingheng Guo; Rui Liu; Qing Chen (Soil Ecology Letters, 2023)

Highly sensitive detection of Salmonella based on dual-functional HCR-mediated multivalent aptamer and amplification-free CRISPR/Cas12a system - Zhaohui Qiao; Liangliang Xue; Mengni Sun; Min Zhang; Min Chen; Xia Xu; Wenge Yang; Rui Wang (Analytica Chimica Acta, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Three Types of Enteromorpha prolifera Bio-Products Based on Different Processing Procedures as Feed Additives in the Diets of Pacific White Shrimp (Litopenaeus vannamei) - Zhibin Zhou; Lubo Wang; Mingqin Dai; Qingyan Gao; Peng Wang; Lili Zhao; Yanlu Li; Rui Xi; Mingchao Pan; Qiang Ma; Houguo Xu; Mengqing Liang; et al. (Fishes, 2023)
A feeding trial was conducted to evaluate the biological activities of Enteromorpha prolifera bio-products in the diets of Pacific white shrimp (Litopenaeus vannamei). Bio-products of E. prolifera included E. prolifera meal, E. prolifera hydrolysate and E. prolifera polysaccharide, which was supplied using different processing procedures. The control diet was supplemented without any E. prolifera bio-products or dietary attractants. Experimental diets were formulated to contain 0.2% and 0.4% of E. prolifera hydrolysate (EPH0.2% and EPH0.4%), 0.03% of E. prolifera polysaccharide (EPP0.03%), 3% of E. prolifera meal (EPM3%), 0.1% of dimethyl-β-propiothetn (DMPT0.1%) and 1% of squid paste (SP1%). Shrimp (~8 g) were randomly distributed in 21 tanks and fed for 44 days. Feed intake showed that 3% of E. prolifera meal and 0.4% of E. prolifera hydrolysate in diets exhibited similar attractant effects as 0.1% of DMPT. Gross qualitative observation showed that the abundance of lipid droplets decreased in hepatopancreas of the EPH0.4% and EPM3% groups, which were supported by hepatopancreas triacylglycerol (TG), where significantly lower concentrations were observed in the EPH0.4% and EPM3% groups compared with the control group. Similarly, TG and low-density lipoprotein cholesterol in serum significantly decreased in the EPH0.4%, EPP0.03% and EPM3% groups compared to the control group. Supplemental E. prolifera bio-products resulted in significantly higher serum glutathione level of EPP0.03% or superoxide dismutase activities of EPH0.4% and EPM3%, but significantly lower serum malondialdehyde level of EPM3%. In addition, tnf-α expression in hepatopancreas was significantly down-regulated in shrimp fed the EPH0.2%, EPH0.4% and EPM3% diets. Based on survival analysis, E. prolifera bio-products improved the resistance of shrimp to hypoxic stresses. Thus, this study confirmed that bio-products of E. prolifera supplied using different processing procedures could be used to reduce the amount of E. prolifera in feed of shrimp without compromising their biological functions.

Acylhydrazone Functionalized Triphenylamine-Based Fluorescent Probe for Cu2+: Tunable Structures of Conjugated Bridge and Its Practical Application - Xiaohong Cheng; Rui Zhang; Jinbo Sun; Ke Xu; Wangnan Li (Journal of Fluorescence, 2023)

Transcriptome analysis reveals the molecular mechanism of different forms of selenium in reducing cadmium uptake and accumulation in wheat seedlings - Xuerong Di; Rui Jing; Xu Qin; Yihua Wei; Xuefeng Liang; Lin Wang; Yingming Xu; Yuebing Sun; Qingqing Huang (Chemosphere, 2023)

A method for obtaining maize phenotypic parameters based on improved QuickShift algorithm - Rui Gao; Shangqing Cui; HaoRan Xu; Qingming Kong; Zhongbin Su; Jinlong Li (Computers and Electronics in Agriculture, 2023)

Dynamic assessment of population exposure to traffic-originated PM2.5 based on multisource geo-spatial data - Hui Zhong; Rui Xu; Hongliang Lu; Yonghong Liu; Meixin Zhu (Transportation Research Part D: Transport and Environment, 2023)

The formins inhibitor SMIFH2 inhibits the cytoskeleton dynamics and mitochondrial function during goat oocyte maturation - Meng-Hao Pan; Rui Xu; Zhi Zheng; Jinfeng Xiong; Haiying Dong; Qiang Wei; Baohua Ma (Theriogenology, 2023)

Assessing resilience of sustainability to climate change in China's cities - Rui Zhao; Xia Li; Ying Wang; Zhenci Xu; Meiyu Xiong; Qian Jia; Fengting Li (Science of The Total Environment, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

A novel 1T-2H MoS2/NaBi(MoO4)2 alternating-phase piezoelectric composites for high-efficient ultrasound-drived piezoelectric catalytic removal of Sildenafil - Qing-rui Zeng; Zi-ang Jia; Xu Liu; Jin-ping Cheng (Process Safety and Environmental Protection, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

TBtools-II: A “one for all, all for one” bioinformatics platform for biological big-data mining - Chengjie Chen; Ya Wu; Jiawei Li; Xiao Wang; Zaohai Zeng; Jing Xu; Yuanlong Liu; Junting Feng; Hao Chen; Yehua He; Rui Xia (Molecular Plant, 2023)

Assessing the potential risks, sources and the relationship between the dissolved and particulate polycyclic aromatic hydrocarbons (PAHs) in the typical semi-enclosed bay, Bohai Bay of China - Kun Lin; Rui Wang; Liju Tan; Shan Jiang; Hongyan Xu; Yali Cao; Jiangtao Wang (Marine Environmental Research, 2023)

A2DWQPE: Adaptive and automated data-driven water quality parameter estimation - Yiyun Hu; Fangling Pu; Chuishun Kong; Rui Yang; Hongjia Chen; Xin Xu (Journal of Hydrology, 2023)

Seepage safety evaluation of high earth-rockfill dams considering spatial variability of hydraulic parameters via subset simulation - Mingyang Xu; Rui Pang; Yang Zhou; Bin Xu (Journal of Hydrology, 2023)

Surface reconstruction of copper foil via electrochemical etching to proliferate CH4 production from CO2 electroreduction - Weicong Xu; Chao Liu; Peijun Li; Hongyun Zeng; Xianjun Lu; Xinyu Li; Tao Li; Rui Xiao (Journal of Cleaner Production, 2023)

Influence of urban extent discrepancy on the estimation of surface urban heat island intensity: A global-scale assessment in 892 cities - Qiquan Yang; Yi Xu; Xiaohua Tong; Ting Hu; Yue Liu; T.C. Chakraborty; Rui Yao; Changjiang Xiao; Shurui Chen; Zonghan Ma (Journal of Cleaner Production, 2023)

SHARAD observations for layered ejecta deposits formed by late-Amazonian-aged impact craters at low latitudes of Mars - Yizhen Ma; Zhiyong Xiao; Fanglu Luo; Wei Cao; Rui Xu (Icarus, 2023)

Highly dispersed Fe/EG catalysts assisted by ammonium citrate and their application in CO2 hydrogenation to olefins - Rui Zhao; Xin Meng; Wenhua Dai; Daoming Jin; Bowen Xu; Fan Xu; Dandan Yang; Zhong Xin (Fuel, 2023)

Lateral flow immunoassay based on gold nanoparticles for rapid and sensitive detection of zoxamide in grape, tomato and cucumber samples - Yuan Cheng; Aihong Wu; Lingling Guo; Maozhong Sun; Rui Gao; Hua Kuang; Chuanlai Xu; Liguang Xu (Food Chemistry, 2023)

A review of the toxic effects of ammonia on invertebrates in aquatic environments - Tian-Xu Zhang; Ming-Rui Li; Chen Liu; Shu-Ping Wang; Zhen-Guang Yan (Environmental Pollution, 2023)

Corrigendum to “Combining functional physiological phenotyping and simulation model to estimate dynamic water use efficiency and infer transpiration sensitivity traits” [Eur. J. Agron. 150 (2023) 126955] - Ting Sun; Rui Cheng; Rujia Jiang; Yunxiu Liu; Yudong Sun; Zhuoyi Wang; Pingping Fang; Xinyang Wu; Kang Ning; Pei Xu (European Journal of Agronomy, 2023)

Janus MXene-based photothermal membrane for efficient and durable water evaporation - Jinbu Su; Yunong Xie; Pengkui Zhang; Rui Yang; Boli Wang; Heng Zhao; Yuyi Xu; Xuli Lin; Jing Shi; Chengbing Wang (Desalination, 2023)

Self-supportive Pd0.2Ni58Fe30O11.8 nanowires for solar-driven self-powered water/seawater splitting with large current density - Guang-Rui Xu; Ning Zhang; Qiyan Sun; Wen Zhang; Zexing Wu; Lei Wang (Chemical Engineering Journal, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

Significantly improved high-temperature capacitive performance in polymer dielectrics utilizing ultra-small carbon quantum dots with Coulomb-blockade effect - Hangchuan Cai; Rui Wang; Bin Gou; Jing Fu; Yujie Zhu; Hao Yang; Jiangang Zhou; Manxi Li; An Zhong; Daoming Zhang; Huasong Xu; Chunhui Bi; et al. (Chemical Engineering Journal, 2023)

Unit cell distortion of ferrierite induced by carbonaceous deposits during skeletal isomerization of 1-butene - Karoline L. Hebisch; Pawel A. Chmielniak; Rick Watson; David Leyshon; Barbara Kimmich; Rui Xu; Benjamin Galfond; Carsten Sievers (Chemical Engineering Journal, 2023)

Macroscale insights into heterogeneous hydrate formation and decomposition behaviors in porous media - Xuan Kou; Xiao-Sen Li; Yi Wang; Rui Xu; Zhao-Yang Chen (Chemical Engineering Journal, 2023)

Transient, printable and recyclable gelatin hydrogels with enhanced mechanical sensing and electromagnetic shielding performance by incorporation of reduced graphene oxide - Rui Yin; Chen Zhang; Youyou Chen; Yu Wang; Qiang Feng; Yaming Liu; Minghan Yu; Yunhuan Yuan; Cheng-Yan Xu; Feihua Liu; Weiwei Zhao (Chemical Engineering Journal, 2023)

Efficient and effective immobilization of tetracycline and copper from wastewater by zero-valent iron fabricated hydrochar derived from walnut peel - Huabin Wang; Dingxiang Chen; Ting Cui; Ran Duan; Xianghong Yan; Yong Zhang; Rui Xu (Bioresource Technology, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Identification of potential genetic causal variants for obesity-related traits using statistical fine mapping - Rui Gong; Jonathan Greenbaum; Xu Lin; Yan Du; Kuan-Jui Su; Yun Gong; Jie Shen; Hong-Wen Deng (Molecular Genetics and Genomics, 2023)

Reduced attention on restricted organochlorine pesticides, whereas still noteworthy of the impact on the deep soil and groundwater: a historical site study in southern China - Changlin Xu; Yue Cai; Rui Wang; Jing Wu; Guoyi Yang; Yahui Lv; Dehong Liu; Yu Deng; Yaqi Zhu; Qing Zhang; Lijun Wang; Shengwei Zhang (Environmental Geochemistry and Health, 2023)

Occurrence, distribution and risk assessment of polycyclic aromatic hydrocarbons in soils around main water source areas of Beijing, China - Bin Li; Liang Zhao; Sining Zhong; Rui An; Ruoqi Ma; Xuming Xu; Qian Chen (Environmental Geochemistry and Health, 2023)

A new anchor-siphon drainage combined method used for slope stabilization - Hong-yue Sun; Xu Wang; Yang Yu; Jun-wei Shu; Tian-long Wang; Rui Luo; Zhao-wei Chu (Journal of Mountain Science, 2023)

Enzymatic DNA repairing amplification-powered construction of an Au nanoparticle-based nanosensor for single-molecule monitoring of cytosine deaminase activity in cancer cells - Wen-jing Liu; Rui Song; Xiao-ran Zou; Dong-ling Li; Qinfeng Xu; Chun-yang Zhang (Analytica Chimica Acta, 2023)

Portable multichannel detection instrument based on time-resolved fluorescence immunochromatographic test strip for on-site detecting pesticide residues in vegetables - Rui Xu; Yaodong Xiang; Zheng Shen; Gaozhen Li; Jiashuai Sun; Peiyu Lin; Xiaofeng Chen; Jingcheng Huang; Haowei Dong; Zhenying He; Wenzheng Liu; Lu Zhang; et al. (Analytica Chimica Acta, 2023)

Meta-analytic and experimental evidence that warmer climate leads to shift from advanced to delayed spring phenology - Jing Guo; Qimei Ma; Hanfeng Xu; Yue Luo; Dashan He; Fucheng Wang; Jiasheng Wu; Yongshuo H. Fu; Jianquan Liu; Rui Zhang; Lei Chen (Agricultural and Forest Meteorology, 2023)

A new modified pterocarpan glycoside from Sophora flavescens - Yan Lin; Jing-Jing Li; Lei He; Qi-Rui Li; Qing-De Long; Xu Zhang; Zhu Zeng (Natural Product Research, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

A petal–cylindrical seismic metamaterial occupying low-frequency wide bandgaps in horizontally stratified soils - Muhammad Muzamil; Hongwu Yang; Rui Xu; Yi Zeng; Pai Peng; Qiujiao Du (Wave Motion, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Source identification and migration fate of metal(loid)s in soil and groundwater from an abandoned Pb/Zn mine - Chiyue Huang; Zhaohui Guo; Tianshuang Li; Rui Xu; Chi Peng; Zilun Gao; Linjian Zhong (Science of The Total Environment, 2023)

Modifying engineered nanomaterials to produce next generation agents for environmental remediation - Muhammad Arslan Ahmad; Muhammad Adeel; Noman Shakoor; Rabia Javed; Muhammad Ishfaq; Yutao Peng; Muhammad Zain; Imran Azeem; Ilyas Ali; Muhammad Usman; Zihao Wu; Gholamreza Gohari; et al. (Science of The Total Environment, 2023)

Hydrogeological controls on chromium enrichment along the groundwater flow path in the Baiyangdian Catchment, North China Plain - Chao Liu; Huaming Guo; Wendi Fan; Rui Xu; Shuangbao Han; Bingying Gao; Bo Zhao; Chunping Jiang (Science of The Total Environment, 2023)

Diversity and function of mountain and polar supraglacial DNA viruses - Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Lin Zang; Rui Zhang; Xiang Xiao; Yi Shi; Zhihao Zhang; Ye Tao; Liping Bai; Bianli Gao; Yunlan Yang; et al. (Science Bulletin, 2023)

A superstable, flexible, and scalable nanofluidic ion regulation composite membrane - Lianmeng Si; Yihan Wu; Hong Xiao; Wensi Xing; Rui Song; Yiju Li; Sha Wang; Xu Liang; Wenshan Yu; Jianwei Song; Shengping Shen (Science Bulletin, 2023)

Nonlinear energy sink-based study on vortex-induced vibration and control of foil-cylinder coupled structure - Dongyang Chen; Rui Xu; Yaochen Lin; Nansha Gao; Guang Pan; Marzocca Pier (Ocean Engineering, 2023)

Numerical study on unsteady cavitation flow and vortex dynamics characteristics around the Delft Twist 11 hydrofoil - Gang Yang; Xi Shen; Bin Xu; Qinghui Meng; Chengxin Chang; Rui Tang; Desheng Zhang (Ocean Engineering, 2023)

Formulas for three-dimensional source localization using multipath time delays measured by asynchronous distributed sensors in deep water - Zhezhen Xu; Hui Li; Rui Duan; Kunde Yang (Ocean Engineering, 2023)

Effects of multi-frequency ultrasound on inactivating Chironomus kiiensis eggs: Evidence from a case study in drinking water treatment plant - Hai-guang Yuan; Rui-jian Zhang; Ye-qin Xu; Zhi Dang; Yong Hu; Qian-Bin Wang; Hao-tao Dong; Jia-xin Liu; Shu-juan Pu; Zhi-li Du; Ying-shi Liu; Zong-jia Zhang (Journal of Water Process Engineering, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

Direct immobilization of Se(IV) from acidic Se(IV)-rich wastewater via ferric selenite Co-precipitation - Zidan Yuan; Rui Su; Xu Ma; Le Yu; Yuanming Pan; Ning Chen; Roman Chernikov; Leo Ka Long Cheung; Reza Deevsalar; Ayetullah Tunc; Liang Wang; Xiangfeng Zeng; et al. (Journal of Hazardous Materials, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Process and mechanism of recovering layered double hydroxides (LDHs) from acid mine drainage (AMD) and synergetic removal of manganese - Qingsheng Xu; Zhengbo Yue; Rui Deng; Xinquan Wang; Xin Chuai; Kai Zhang; Jin Wang (Journal of Environmental Chemical Engineering, 2023)

Metagenomic analysis reveals microbial metabolic potentials alterations under antibiotic stress during sludge anaerobic digestion - Yinping Xiang; Weiping Xiong; Rui Xu; Zhaohui Yang; Yanru Zhang; Meiying Jia; Haihao Peng (Journal of Environmental Chemical Engineering, 2023)

Novel TFC membrane with PMIA thin-film as active layer fabricated by the T-FLO technique for dye desalination - Pingping Li; Zhenliang Xu; Dibakar Pandaya; Yinxin Fang; Linglin Gao; Rui Ding; Kaiqi Yu (Journal of Environmental Chemical Engineering, 2023)

The metal-organic frameworks as unique platform for photocatalytic CO2 conversion to liquid fuels - Xiahong Xu; Kangle Xie; Junjie Hu; Suijun Liu; Hong Zhong; He-Rui Wen (Journal of Environmental Chemical Engineering, 2023)

A spectral-temporal constrained deep learning method for tree species mapping of plantation forests using time series Sentinel-2 imagery - Zehua Huang; Liheng Zhong; Feng Zhao; Jin Wu; Hao Tang; Zhengang Lv; Binyuan Xu; Longfei Zhou; Rui Sun; Ran Meng (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

Characterizing bourbon whiskey via the combination of LC-MS and GC–MS based molecular fingerprinting - Rui Xu; Li Chen; Huan Zhang; Michael W. Crowder; Jiangjiang Zhu (Food Chemistry, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Crop cultivar mixtures stabilize productivity, partly via facilitation, when conditions are less benign - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Jian-Hao Sun; Jian-Hua Zhao; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2023)

Acetylcholine (ACh) enhances Cd tolerance through transporting ACh in vesicles and modifying Cd absorption in duckweed (Lemna turionifera 5511) - Lin Yang; Xu Ma; Yuhan Guo; Yuman He; Yunwen Yang; Wenqiao Wang; Ziyi Xu; Zhaojiang Zuo; Ying Xue; Rui Yang; Bing Han; Jinsheng Sun (Environmental Pollution, 2023)

Combining functional physiological phenotyping and simulation model to estimate dynamic water use efficiency and infer transpiration sensitivity traits - Ting Sun; Rui Cheng; Rujia Jiang; Yunxiu Liu; Yudong Sun; Zhuoyi Wang; Pingping Fang; Xinyang Wu; Kang Ning; Pei Xu (European Journal of Agronomy, 2023)

Seismic and hydrological triggers for a complex cascading geohazard of the Tianmo Gully in the southeastern Tibetan Plateau - Rui Guo; Liming Jiang; Zhida Xu; Chao Li; Ronggang Huang; Zhiwei Zhou; Tao Li; Yi Liu; Hansheng Wang; Xuanmei Fan (Engineering Geology, 2023)

Characterization of a gE/gI/TK gene-deleted pseudorabies virus variant expressing the Cap protein of porcine circovirus type 2d - Rui-Qin Xu; Lin-Qing Wang; Hui-Hua Zheng; Run-Bo Tian; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Hybrid tribo/piezoelectric nanogenerator textile derived from 3D interlocked parallel-arranged yarns for bio-motion energy harvesting and tactile sensing - Lin Liu; Yuantao Li; Muchun Xu; Rui Tao; Qiao Zhong; Xi Yang; Shixia Lan; Jiyang Xie; Guo Chen; Yongyun Mao; Wanbiao Hu (Chemical Engineering Journal, 2023)

Highly stable and selective Pt/TS-1 catalysts for the efficient nonoxidative dehydrogenation of propane - Weilong Hou; Kehang Lin; Xiangyu Zhang; Bowen Xu; Yuexia Wang; Xinqing Lu; Yijing Gao; Rui Ma; Yanghe Fu; Weidong Zhu (Chemical Engineering Journal, 2023)

Molten Salt-Mediated Surface Reconstruction Induced Orientation-Growth of 1D/2D Heterostructure for High-Sensitivity H2S Gas Sensing - Xuan-Yu Yang; Rui-Jie Zhao; Ke-Feng Xie; Hua Xu; Shao-Ming Fang; Yong-Hui Zhang (Chemical Engineering Journal, 2023)

Dual network hydrogel coatings based on recombinant mussel protein with enhanced antibacterial and super-lubrication properties for urinary catheter applications - Yubo Hu; Youzhi Qiao; Peng Lei; Yian Gu; Liang Sun; Yibin Qiu; Sha Li; Hong Xu; Rui Wang (Chemical Engineering Journal, 2023)

A novel starch-based ethanol gel with contact-killing bacteria to cut off contact transmission of bacteria - Fu-Xiang Wei; Tian-Rui Zhou; Shao-Wei Zhong; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Chemical Engineering Journal, 2023)

Multifunctional carboxylated cellulose nanofibers/exfoliated bentonite/Ti3C2 aerogel for efficient oil adsorption and recovery: The dual effect of exfoliated bentonite and MXene - Rui Tang; Ya Hu; Jingyuan Yan; Shiqi Xu; Yinlong Wang; Jinsheng Yan; Dankui Liao; Hanbing Zhang; Zhangfa Tong (Chemical Engineering Journal, 2023)

Microwave-coordinated KOH directionally modulated N/O co-doped porous biochar from Enteromorpha and its structure–effect relationships in efficient CO2 capture - Juan Luo; Yi Chen; Huimin Huang; Rui Ma; Ning Ma; Feng Yan; Jiyun Xu; Junshen Zhang; Jiashan Chen; Shichang Sun (Chemical Engineering Journal, 2023)

Intrinsic reaction selectivity between gaseous HCl and SO2 over ethanol-hydrated CaO adsorbent in coal-fired flue gas dechlorination - Xiaoshuo Liu; Rui Wang; Xinze Geng; Ao Shen; Cong Chen; Yifan Xu; Xunlei Ding; Yufeng Duan; Shilin Zhao (Chemical Engineering Journal, 2023)

A multilayer perceptron-based fast sunlight assessment for the conceptual design of residential neighborhoods under Chinese policy - Can Jiang; Xiong Liang; Yu-cheng Zhou; Yong Tian; Shengli Xu; Jia-Rui Lin; Zhiliang Ma; Shiji Yang; Hao Zhou (Building and Environment, 2023)

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice - Jingzhou Li; Fei Song; Ruolan Chen; Jinjuan Yang; Jie Liu; Li Huang; Fuyu Duan; Meng Kou; Boon Xuan Lian; Xiaoxia Zhou; Weimin Han; Liang Mao; et al. (Stem Cell Reviews and Reports, 2023)

Lactiplantibacillus plantarum Regulated Intestinal Microbial Community and Cytokines to Inhibit Salmonella typhimurium Infection - Rui-Han Liu; An-Qi Sun; Ye Liao; Zheng-Xu Tang; Shi-Han Zhang; Xin Shan; Jing-Tao Hu (Probiotics and Antimicrobial Proteins, 2023)

Neglected Adult Tinea Capitis in South China: A Retrospective Study in Nanchang, Jiangxi Province, from 2007 to 2021 - Yun Jin; Chengfang Geng; Oliver Blechert; Qing Jiang; Rui Xu; Yunpeng Luo; Xinyi Fan; Guirong Qiu; Ping Zhan (Mycopathologia, 2023)

Urine 2-hydroxyphenanthrene is associated with current asthma: evidence from NHANES 2007–2012 - Lingyi Lu; Tingfeng Mao; Rui Xu; Lanxia Liu; Jiefeng Qian; Kai Yang; Anjie Yuan; Xinyue Wang; Rong Ni (International Archives of Occupational and Environmental Health, 2023)

Risk factors for thrombocytopenia in patients receiving linezolid therapy: a systematic review and meta-analysis - Dan Zhang; Yasi Xu; Xiang Wang; Leping Hou; Mengyu Xing; Shuang Xu; Rui Guo; Ying Luo (European Journal of Clinical Pharmacology, 2023)

Asteroid landing analysis for multi-node probe based on spring damping device - Bang Wang; Rui Xu; Zhaoyu Li; Shengying Zhu; Siyao Lu; Yue Gao (Advances in Space Research, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

Epidemiology, genetic diversity, and evolutionary dynamics of Tembusu virus - Peng Zhou; Bin Ma; Yuan Gao; Yumin Xu; Zhuofei Li; Hui Jin; Rui Luo (Archives of Virology, 2023)

Phylogenetic distance–decay patterns are not explained by local community assembly processes in freshwater lake microbial communities - Yian Gu; Zhidan Li; Peng Lei; Rui Wang; Hong Xu; Ville‐Petri Friman (Environmental Microbiology, 2023)
While water and sediment microbial communities exhibit pronounced spatio‐temporal patterns in freshwater lakes, the underlying drivers are yet poorly understood. Here, we evaluated the importance of spatial and temporal variation in abiotic environmental factors for bacterial and microeukaryotic community assembly and distance–decay relationships in water and sediment niches in Hongze Lake. By sampling across the whole lake during both Autumn and Spring sampling time points, we show that only bacterial sediment communities were governed by deterministic community assembly processes due to abiotic environmental drivers. Nevertheless, consistent distance–decay relationships were found with both bacterial and microeukaryotic communities, which were relatively stable with both sampling time points. Our results suggest that spatio‐temporal variation in environmental factors was important in explaining mainly bacterial community assembly in the sediment, possibly due lesser disturbance. However, clear distance–decay patterns emerged also when the community assembly was stochastic. Together, these results suggest that abiotic environmental factors do not clearly drive the spatial structuring of lake microbial communities, highlighting the need to understand the role of other potential drivers, such as spatial heterogeneity and biotic species interactions.

Editorial: Noise and vibrations in offshore wind farms and their impact on aquatic species - Rui He; Apostolos Tsouvalas; Xiaomei Xu; Lijun Dong (Frontiers in Marine Science, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Mn(VII) enhanced by CaSO3 to remove trace organic pollutants in high salt organic wastewater: Further enhancement of salinity - Linsong Cheng; Yuanxiang Mao; Lei Jiang; Rui Ma; Jiangsen Ma; Yiyuan Zhuo; Qiushi Shen; Caocong Liu; Liuwei Zhao; Xiaoyi Xu; Fangying Ji (Chemosphere, 2023)

Adjusting effects of pyrolytic volatiles interaction in char to upgrade oil by swelling waste nylon-tire - Rui Huang; Qiangqiang Ren; Jialin Zhang; Limo He; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Song Hu; Jun Xiang (Waste Management, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Loss of amino acids 67-76 in the neuraminidase protein under antibody selection pressure alters the tropism, transmissibility and innate immune response of H9N2 avian influenza virus in chickens - Jianjun Zhang; Quan Li; Rui Zhu; Shunshun Xu; Shifeng Wang; Huoying Shi; Xiufan Liu (Veterinary Microbiology, 2023)

Exploring decision-making mechanisms for the metro-based underground logistics system network expansion: An example of Beijing - Zhilong Chen; Wanjie Hu; Yuanxian Xu; Jianjun Dong; Kai Yang; Rui Ren (Tunnelling and Underground Space Technology, 2023)

Seismic failure probability analysis of slopes via stochastic material point method - Dezhi Zai; Rui Pang; Bin Xu; Jun Liu (Soil Dynamics and Earthquake Engineering, 2023)

Uncertainty in China's food self-sufficiency: A dynamic system assessment - Xinyuan Liang; Xiaobin Jin; Xiaoxiao Xu; Hefeng Chen; Jing Liu; Xuhong Yang; Weiyi Xu; Rui Sun; Bo Han; Yinkang Zhou (Sustainable Production and Consumption, 2023)

Reducing carbon footprints and increasing net ecosystem economic benefits through dense planting with less nitrogen in double-cropping rice systems - Wentao Zhou; Wenfei Long; Hongrui Wang; Pan Long; Ying Xu; Kangyu Zhong; Rui Xiong; Feipeng Xie; Fugui Chen; Zhiqiang Fu (Science of The Total Environment, 2023)

Global prevalence and factors affecting the level of Cryptosporidium contamination in soil: A systematic review, meta-analysis, and meta-regression - Mu-Ran Zuo; Xiao-Ting Li; Rui-Zhe Xu; Wen-Chao Sun; Hany M. Elsheikha; Wei Cong (Science of The Total Environment, 2023)

Spatial variability of arsenic fractionation in an abandoned arsenic-containing mine: Insights into soil particle sizes and quantitative mineralogical analysis - Hongzhen Ran; Zhaohui Guo; Liwen Yi; Xiyuan Xiao; Rui Xu; Zhihao Hu; Tianshuang Li (Science of The Total Environment, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

PbWRKY26 positively regulates malate accumulation in pear fruit by activating PbMDH3 - Meiyi Yang; Junxing Song; Xu Zhang; Ruitao Lu; Azheng Wang; Rui Zhai; Zhigang Wang; Chengquan Yang; Lingfei Xu (Journal of Plant Physiology, 2023)

Anaerobic selenite-reducing bacteria and their metabolic potentials in Se-rich sediment revealed by the combination of DNA-stable isotope probing, metagenomic binning, and metatranscriptomics - Rui Xu; Max Kolton; Wan Tao; Xiaoxu Sun; Pingzhou Su; Duanyi Huang; Miaomiao Zhang; Zhaohui Yang; Zhaohui Guo; Hanbing Gao; Qi Wang; Baoqin Li; et al. (Journal of Hazardous Materials, 2023)

A novel framework to improve the consistency of water quality attribution from natural and anthropogenic factors - Shanlin Tong; Wenpan Li; Jie Chen; Rui Xia; Jingyu Lin; Yan Chen; Chong-Yu Xu (Journal of Environmental Management, 2023)

Structure, rheology, and antifreeze property of the exopolysaccharide from Naematelia aurantialba through basidiospore fermentation - Tao Sun; Xiaoyi Xu; Yuhang Ma; Hao jiang; Kai Yang; Rui Wang; Yian Gu; Sha Li; Yibin Qiu; Dafeng Sun; Hong Xu; Peng Lei (Food Hydrocolloids, 2023)

Temporary stress regime reversal immediately after the complete release of the localized compressive stress by the 2021 Luxian Ms 6.0 earthquake, Sichuan Basin - Chaoliang Wang; Chuntao Liang; Jiangtao Liao; Zhenxing Yao; Rui Xu; Yihai Yang (Earth and Planetary Science Letters, 2023)

Enhanced catalytic nitrophenol reduction via highly porous hollow silica nanospheres stabilized Au nanoclusters - Ru Hu; Rui Xu; Zizhu Wang; Junyou Wang; Shenghu Zhou (Chemical Engineering Journal, 2023)

Insights on rational design and regulation strategies of Prussian blue analogues and their derivatives towards high-performance electrocatalysts - Yu-Rui Ji; Ya-Fei Guo; Xu Liu; Peng-Fei Wang; Ting-Feng Yi (Chemical Engineering Journal, 2023)

Mechanical vibration reactor achieves CO2 methanation assisted by ruthenium modified nickel milling balls - Keran Lv; Rui Tu; Lihui Xiao; Wei Wei; Yuchun Xu; Guoqing Ren; Rong Huang; Weiqiao Deng; Tie Yu (Chemical Engineering Journal, 2023)

Dual-layer drug release system based on ureteral stents inhibits the formation of ureteral stricture - Zhiduan Cai; Wenjun Luo; Haoquan Zhuang; Congling Ren; Xiaolin Pan; Yuyu Xu; Haoran Wang; Xiezhao Li; Yaoji Yuan; Rui Zhu; Xiangyu Zhan; Lin Jin; et al. (Chemical Engineering Journal, 2023)

Boosted photogenerated charge carrier separation by synergy of oxygen and phosphorus co-doping of graphitic carbon nitride for efficient 2-chlorophenol photocatalytic degradation - Zhuzhu Zhang; Qimeng Sun; Rui Ji; Dongyun Chen; Najun Li; Hua Li; Qingfeng Xu; Huilong Dong; Jianmei Lu (Chemical Engineering Journal, 2023)

Microbial metabolism and humic acid formation in response to enhanced copper and zinc passivation during composting of wine grape pomace and pig manure - Yingchao Zhang; Yang Xu; Xinlong Yu; Jinkang Li; Guang Chen; Shuaijie Wang; Yanping Xu; Rui Xu; Baohai Zhang; Hongqiong Zhang (Bioresource Technology, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Cutting Efficiency of a Newly Developed Incubator-Based Laser Cutting Method and Its Effects on Potato Tissue Culture Plantlet Growth - Tao Xu; Hongbing Duan; Xingkui Cai; Rui Yang; Feihu Yao; Benfang Tan; Fengshun Liu (Potato Research, 2023)

The biocontrol agent Bacillus velezensis T-5 changes the soil bacterial community composition by affecting the tomato root exudate profile - Yian Gu; Weina Liang; Zhidan Li; Sijie Liu; Sun Liang; Peng Lei; Rui Wang; Nan Gao; Sha Li; Zongqi Xu; Hong Xu (Plant and Soil, 2023)

Development and validation a prognostic model based on natural killer T cells marker genes for predicting prognosis and characterizing immune status in glioblastoma through integrated analysis of single-cell and bulk RNA sequencing - Jiahe Hu; Lei Xu; Wenchao Fu; Yanan Sun; Nan Wang; Jiheng Zhang; Chengyun Yang; Xiaoling Zhang; Yuxin Zhou; Rongfang Wang; Haoxin Zhang; Ruishu Mou; et al. (Functional & Integrative Genomics, 2023)

Prediction of landslide block movement based on Kalman filtering data assimilation method - Yong Liu; Qing-jie Xu; Xing-rui Li; Ling-feng Yang; Hong Xu (Journal of Mountain Science, 2023)

Do not ignore the effects of phosphorus and potassium addition on microbial carbon use efficiency - Chenyang Zhang; Liyang Sun; Yichao Rui; Yue Li; Yiqi Luo; Minggang Xu; Andong Cai (Global Change Biology, 2023)

Otolith microchemistry reveals various habitat uses and life histories of Chinese gizzard shad Clupanodon thrissa in the Min River and the estuary, Fujian Province, China - Qing Xu; Qing-qiang Ren; Tao Jiang; Chen-rui Jiang; Lü-ping Fang; Ming-zhe Zhang; Jian Yang; Min Liu (Fisheries Research, 2023)

A study on the gaseous radionuclide dispersion in the highway across urban blocks: Effects of the urban morphology, roadside vegetation and leakage location - Rui Jia; Jianzhi Yang; Xiaowei Zhu; Fusuo Xu; Liping Wang (Sustainable Cities and Society, 2023)

Frequency effect on mechanical properties of calcareous sand under cyclic traffic loading - Xiaoxi Rui; Yang Shen; Yinghao Ma; Junhong Xu (Soil Dynamics and Earthquake Engineering, 2023)

The potential of biochar as a microbial carrier for agricultural and environmental applications - Shiv Bolan; Deyi Hou; Liuwei Wang; Lauren Hale; Dilfuza Egamberdieva; Priit Tammeorg; Rui Li; Bing Wang; Jiaping Xu; Ting Wang; Hongwen Sun; Lokesh P. Padhye; et al. (Science of The Total Environment, 2023)

Quality assurance and quality control throughout microplastic analysis - Long Zhu; Yanyan Yu; Jingying Zhu; Rui Zuo; Qiujin Xu; Lihui An; Yanhua Qian (Science of The Total Environment, 2023)

Soil acidification in a tailing area of ionic rare earth in Southeast China - Zhe Xu; Jin-ling Yang; Yue Zhao; Rui Hao; Gan-lin Zhang (Science of The Total Environment, 2023)

Theory, framework, and methodology for physical lifespan prediction of hazardous waste landfills - Xu Ya; Yao Guangyuan; Liu Yuqiang; Liu Jingcai; Xiang Rui; Qian Can (Science of The Total Environment, 2023)

Dynamic probabilistic risk assessment of emergency response for intelligent coal mining face system, case study: Gas overrun scenario - Yan Zhang; Yu-Hao Wang; Xu Zhao; Rui-Peng Tong (Resources Policy, 2023)

Enhanced selective nitrate-to-nitrogen electrocatalytic reduction by CNTs doped Ni foam/Cu electrode coupled with Cl− - Xinrui Liu; Rui Guo; Xia Qin; Cuicui Xu (Journal of Water Process Engineering, 2023)

Effects of gums on 3D printing performance of Pleurotus eryngii powder - Anqi He; Juan Xu; Qiuhui Hu; Liyan Zhao; Gaoxing Ma; Lei Zhong; Rui Liu (Journal of Food Engineering, 2023)

A “smart-sensing” bactericidal protein-based Pickering emulsion - Lishan Yao; Rui Wang; Shurui Peng; Zhenbin Liu; Hongbo Li; Dan Xu; Liangbin Hu; Haizhen Mo (Journal of Food Engineering, 2023)

Construction of S-scheme Zn0.2Cd0.8S/biochar aerogel architectures for boosting photocatalytic hydrogen production under sunlight irradiation - Chonghai Deng; Lulu Peng; Xiaohui Ling; Tao Wang; Rui Xu; Yibin Zhu; Chenchen Wang; Xuehui Qian; Lili Wang; Yiping Wu; Hanmei Hu; Yongsheng Han (Journal of Cleaner Production, 2023)

Decorative ZIF-8 covered facet-dependent Cu2O toward highly efficient adsorption by reduction U(VI) to U(IV) - Xiaomei Zhang; Nina Yan; Min Wang; Xizhi Jiang; Rui Xu; Min Feng; Lei Xu; Shaochun Tang (Journal of Environmental Chemical Engineering, 2023)

Geological ahead-prospecting method while TBM drilling using improved seismic interferometry method: A case - Lei Chen; Lei Hao; Xinji Xu; Fengkai Zhang; Rui Wang (Journal of Applied Geophysics, 2023)

Structure-guided camera localization for indoor environments - Qing Li; Rui Cao; Kanglin Liu; Zongze Li; Jiasong Zhu; Zhenyu Bao; Xu Fang; Qingquan Li; Xianfeng Huang; Guoping Qiu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Semantic segmentation of urban building surface materials using multi-scale contextual attention network - Fan Xu; Man Sing Wong; Rui Zhu; Joon Heo; Guoqiang Shi (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Nickel based catalyst supported by carbon aerogel prepared from waste pomelo peel to crack ethanol for hydrogen production: Catalytic performance and mechanism - Jialin Zhang; Song Hu; Yong Ding; Rui Huang; Qiangqiang Ren; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Jun Xiang (Fuel, 2023)

Formation of giant copper deposits in Tibet driven by tearing of the subducted Indian plate - Zengqian Hou; Rui Wang; Haijiang Zhang; Yuanchuan Zheng; Sheng Jin; Hans Thybo; Roberto F. Weinberg; Bo Xu; Zhiming Yang; Ao-Wei Hao; Lei Gao; Letian Zhang (Earth-Science Reviews, 2023)

Plasticity inverse analysis for Zipingpu concrete-faced rockfill dam based on advanced cloud surrogate model via improved Jaya optimization algorithm - Bin Xu; Yichuan Li; Rui Pang (Computers and Geotechnics, 2023)

Selective pollutant degradation with a novel persulfate activation cell resistant to environmental interference - Hui-Shan Meng; Shu-Zhen He; Mei-Mei Wang; Jia-Rui Xi; Jia-Tai Wen; Hong-Wei Luo; Wei-Kang Wang; Juan Xu (Chemical Engineering Journal, 2023)

Self-shedding of multifunctional biomolecular nanocarriers for H-FABP monitoring in magnetic separation self-powered photoelectrochemical and colorimetric immunoassay platform - Dongquan Leng; Rui Xu; Xiang Ren; Hongmin Ma; Lei Liu; Qin Wei; Huangxian Ju (Chemical Engineering Journal, 2023)

Controlled release of Lactiplantibacillus plantarum by colon-targeted adhesive pectin microspheres: Effects of pectin methyl esterification degrees - Danling Xu; Xiaogan Zhao; Ghahvechi Chaeipeima Mahsa; Kai Ma; Changliang Zhang; Xin Rui; Mingsheng Dong; Wei Li (Carbohydrate Polymers, 2023)

Graph neural network-based spatio-temporal indoor environment prediction and optimal control for central air-conditioning systems - Jing Zhang; Fu Xiao; Ao Li; Tianyou Ma; Kan Xu; Hanbei Zhang; Rui Yan; Xing Fang; Yuanyang Li; Dan Wang (Building and Environment, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Spatial distribution of landslide shape induced by Luding Ms6.8 earthquake, Sichuan, China: case study of the Moxi Town - Xuemei Liu; Pengcheng Su; Yong Li; Zhaoxu Xia; Siyuan Ma; Rui Xu; Yao Lu; Dahu Li; Heng Lu; Renmao Yuan (Landslides, 2023)

Analysis of the Sedimentary Characteristics of a Modern Distributive Fluvial System: A Case Study of the Great Halten River in the Sugan Lake Basin, Qinghai, China - Xianghui Zhang; Changmin Zhang; Adrian Hartley; Qinghai Xu; Wenjie Feng; Taiju Yin; Rui Zhu (Journal of Earth Science, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Neurodevelopmental effects of maternal folic acid supplementation: a systematic review and meta-analysis - Hanxiao Chen; Lang Qin; Rui Gao; Xiaolei Jin; Kemin Cheng; Sirui Zhang; Xiao Hu; Wenming Xu; Hongjing Wang (Critical Reviews in Food Science and Nutrition, 2023)

Distribution, sources and influencing factors of organic carbon in the surface sediments of the coastal tidal flats in Jiangsu Province - Rui Zhao; Xinrui Dong; Qing Liu; Min Xu; Yifei Zhao (Frontiers in Marine Science, 2023)
Coastal tidal flats are situated in the interaction zone between the ocean and land and are vulnerable to natural changes, human activities, and global changes; these areas serve as an important mixing zone and burial area for carbon and nitrogen storage. Coastal tidal flats contribute significantly to the global carbon cycle due to their high biological productivity, high sedimentation rate, and low decomposition rate. However, there is a lack of research on the sources and influencing factors of organic carbon in surface sediments in the coastal tidal flat area of Jiangsu Province. In this study, fourteen surface sediment samples were collected from the Jiangsu coastal tidal flats, and the distribution of organic carbon was analyzed. The sources and influencing factors of sediment organic carbon were also investigated by analyzing the contents, ratios and stable isotopes of carbon and nitrogen in the sediments. The results indicated that the total organic carbon (TOC) and total nitrogen (TN) contents in the surface sediments of Jiangsu coastal tidal flats ranged from 0.09% to 0.82% and from 0.01% to 0.1%, with mean values of 0.36% and 0.04%, respectively, and that there was a significant positive correlation between TOC and TN. Moreover, the high-value areas were located mostly along the borders or in sections covered in vegetation, whereas the mudflat areas without vegetation had lower values. Considering the status of the Jiangsu coastal zone, the abandoned Yellow River estuary, Yangtze River inlet, marine benthic microalgae, C3 plants and C4 plants were selected as end members of organic carbon concentrations. The contributions of different sources were quantified using a Bayesian mixture model (MixSIAR). Among them, the abandoned Yellow River estuary and Yangtze River inlet contributed 28.1% and 19.3%, respectively, followed by marine benthic microalgae with a contribution of 26%, whereas C3 and C4 plants made limited contributions of 9% and 8.8%, respectively. Additionally, the sediment particle size, hydrodynamics, and tidal flat vegetation such as Spartina alterniflora were the key factors influencing the organic carbon distribution. In general, this study contributes to a better understanding of the biogeochemical processes and sources of organic carbon in coastal tidal flats. It also provides a solid foundation for the creation of carbon sink measures in nearshore tidal flats.

Degradation of trichloroethylene by double dielectric barrier discharge (DDBD) plasma technology: Performance, product analysis and acute biotoxicity assessment - Xu-Rui Hu; Yong-Chao Wang; Zhen Tong; Can Wang; Er-Hong Duan; Meng-Fei Han; Hsing-Cheng Hsi; Ji-Guang Deng (Chemosphere, 2023)

Iron-rich red mud and iron oxide-modified biochars: A comparative study on the removal of Cd(II) and influence of natural aging processes - Huabin Wang; Dingxiang Chen; Yi Wen; Yong Zhang; Ying Liu; Rui Xu (Chemosphere, 2023)

A method establishment and application for biofilm quorum quenching activity assay - Zhen Tong; Yong-Chao Wang; Guan-Yu Jiang; Xu-Rui Hu; Yi-Mei Xue; Can Wang (Chemosphere, 2023)

Magnetic anaerobic granular sludge for sequestration and immobilization of Pb - Rui Zhou; Han Li; Chengshuai Liu; Yizhang Liu; Jyh-Fu Lee; Yu-Jung Lin; Zhang Yan; Zhangyi Xu; Xiaoyun Yi; Chunhua Feng (Water Research, 2023)

Lithium recovery and solvent reuse from electrolyte of spent lithium-ion battery - Rui Xu; Shuya Lei; Tianyu Wang; Chenxing Yi; Wei Sun; Yue Yang (Waste Management, 2023)

Impacts of urban morphology on sensible heat flux and net radiation exchange - Jinxin Yang; Zhifeng Wu; Massimo Menenti; Man Sing Wong; Yanhua Xie; Rui Zhu; Sawaid Abbas; Yong Xu (Urban Climate, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Inhibitory effect of polyethylene microplastics on roxarsone degradation in soils - Jie-wen Ma; Ya-qing Wu; Chen-Lu Xu; Zhuan-xi Luo; Rui-lian Yu; Gong-ren Hu; Yu Yan (Journal of Hazardous Materials, 2023)

Systematic exploration of transcriptional responses of interspecies interaction between Karenia mikimotoi and Prorocentrum shikokuense - Jian-Wei Zheng; Guo-Hui He; Rui-Xia Xu; Xiang Wang; Hong-Ye Li; Wei-Dong Yang (Harmful Algae, 2023)

Risk source identification and diffusion trends of metal(loid)s in stream sediments from an abandoned arsenic-containing mine - Jie Cao; Zhaohui Guo; Hongzhen Ran; Rui Xu; Richmond Anaman; Huizhi Liang (Environmental Pollution, 2023)

Application and improvement of a stress partition framework-based methane hydrate-bearing sediment constitutive model for wide range confining stress - Jialin Xu; Rui Wang; Chengshun Xu; Yuxi Wang; Jianhong Zhang (Computers and Geotechnics, 2023)

A novel fluorescent probe for imaging endogenous hydrogen sulfide in living cells and mice models of acute liver injury - Kai Wang; Rui Guo; Xu-Yang Chen; Xiu-Lin Li; Zhi-Gang Hu; Xiao Wang; Chao-Yue Wang; Ya-Juan Qin; Kun Yao; Yu-Shun Yang (Chemical Engineering Journal, 2023)

Ball-milling-induced phase transition of ZrO2 promotes selective oxidation of glycerol to dihydroxyacetone over supported PtBi bimetal catalyst - Pan Luo; Jianyue Wang; Wenjuan Rui; Ruilin Xu; Zhiyuan Kuai; Dan Yang; Xiaoyue Wan; Chunmei Zhou; Yanhui Yang; Yihu Dai (Chemical Engineering Journal, 2023)

Benzene abatement catalyzed by Ceria-Supported platinum nanoparticles and single atoms - Jing Liu; Xue Fang; Daoqing Liu; Xiaolei Hu; Tian Qin; Junxiao Chen; Rui Liu; Dongrun Xu; Weiye Qu; Yangyang Dong; Liwei Chen; Zhen Ma; et al. (Chemical Engineering Journal, 2023)

Facet-Controlled Cu-doped and K-promoted Fe2O3 nanosheets for efficient CO2 hydrogenation to liquid hydrocarbons - Chuan Qin; Yixiong Du; Ke Wu; Yanfei Xu; Rui Li; Haifeng Fan; Di Xu; Mingyue Ding (Chemical Engineering Journal, 2023)

Methanol tolerance upgrading of Proteus mirabilis lipase by machine learning-assisted directed evolution - Rui Ma; Yingnan Li; Meng Zhang; Fei Xu (Systems Microbiology and Biomanufacturing, 2023)

Lead change of a HIF-2α antagonist guided by multiparameter optimization and utilization of an Olp→π*Ar interaction - Paul M. Wehn; Song Yang; Jonas A. Grina; James P. Rizzi; Stephen T. Schlachter; Bin Wang; Rui Xu; Hanbiao Yang; Xinlin Du; Guangzhou Han; Keshi Wang; Robert M. Czerwinski; et al. (Medicinal Chemistry Research, 2023)

A Novel D-π-A Type Fluorescent Probe for Cu2+ Based on Styryl-Pyridinium Salts Conjugating Di-(2-picolyl)amine (DPA) Units - Rui Cao; Mengyu Zhang; Wen Tang; Jing Wu; Meixiang Wang; Xiaoxiao Niu; Zhaodi Liu; Fuying Hao; Huajie Xu (Journal of Fluorescence, 2023)

Selenium toxicity and bioaccumulation in selenium-enriched fly (Chrysomya megacephala) maggots - Rui Jie Peng; Chao Zheng; Zhan Biao Yang; Xiao Xun Xu; Ming Hung Wong; Yu Bon Man; Zhang Cheng (Environmental Geochemistry and Health, 2023)

A robust activatable two-photon fluorescent probe for endogenous formaldehyde biomarker visualization diagnosis and evaluation of diabetes mellitus - Jiangyan Wang; Jiangfeng Li; Lizhen Xu; Dan Tan; Rui Guo; Weiying Lin (Analytica Chimica Acta, 2023)

Removal of toilet paper fibers from residential wastewater: a life cycle assessment - Xiaoyu Wang; Guoqiang Liu; Weimin Sun; Zhiguo Cao; Huaqing Liu; Yiqun Xiong; Baoqin Li; Xiaoxu Sun; Yongbin Li; Rui Xu; Duanyi Huang; Pin Gao (Environmental Science and Pollution Research, 2023)

Circular RNA circAKIRIN2 participates in the process of stress-induced immunosuppression affecting immune response to infectious bursal disease virus vaccine in chicken - Yufei Tian; Xiaoli Ma; Yi Jiang; Jianwei Han; Rui Zhang; Xinxin Xu; Wei Zhang; Chaolai Man (Veterinary Microbiology, 2023)

Toxicity and synergistic effect of secondary metabolites isolated from the endophytic fungus LS-Y-1 of Rhododendron przewalskii against Tribolium castaneum - Junyu Liang; Haoshu Wu; Xudong Wang; Rui Feng; Peiyu Lu; Jie Xu; Weibao Kong; Yuan Li (South African Journal of Botany, 2023)

The discovery of 3-fluoroalkyl indoles as potential antifungal agents to control tomato gray mold caused by Botrytis cinerea - Rui Feng; Fei Liu; Yan Wang; Shu Xu; Wuzhang Liu; Siwei Qiao; Songtao Liu; Yu Chen; Xu Feng; Qizhi Wang; Weidong Rao (Phytochemistry Letters, 2023)

The RLCK–VND6 module coordinates secondary cell wall formation and adaptive growth in rice - Shaoxue Cao; Yan Wang; Yihong Gao; Rui Xu; Jianing Ma; Zuopeng Xu; Keke Shang-Guan; Baocai Zhang; Yihua Zhou (Molecular Plant, 2023)

Efficient emerging contaminants (EM) decomposition via peroxymonosulfate (PMS) activation by Co3O4/carbonized polyaniline (CPANI) composite: Characterization of tetracycline (TC) degradation property and application for the remediation of EM-polluted water body - Jin Qian; Xiaohui Mi; Zhijie Chen; Weihang Xu; Wen Liu; Rui Ma; Yichu Zhang; Yufei Du; Bing-Jie Ni (Journal of Cleaner Production, 2023)

Microwave-induced preparation of MgO-loaded N-rich porous biochar from marine biomass for efficient CO2 capture and mechanism exploration via theoretical calculation - Juan Luo; Yi Chen; Xi Zhang; Rui Ma; Huimin Huang; Shichang Sun; Junhao Lin; Feng Yan; Jiyun Xu (Journal of Cleaner Production, 2023)

Deciphering riverine dissolved organic matter biodegradation: Evidence from three-dimensional fluorescence - Rong Xu; Jing Zhang; Jianwei Li; Rui Liu; Maofei Ni; Guangneng Zeng (Journal of Environmental Chemical Engineering, 2023)

Magnetic biochar promotes the risk of mobile genetic elements propagation in sludge anaerobic digestion - Yanru Zhang; Yinping Xiang; Rui Xu; Jing Huang; Jiaqin Deng; Xuan Zhang; Zijian Wu; Zhongliang Huang; Zhaohui Yang; Jingliang Xu; Wenlong Xiong; Hui Li (Journal of Environmental Management, 2023)

Nanoencapsulation-based fabrication of eco-friendly pH-responsive pyraclostrobin formulations with enhanced photostability and adhesion to leaves - Yingjian Ma; Linjie Li; Rui Zhao; Zhe Sun; Yinmin Wang; Meng Yu; Shouhe Pan; Xinyu Guo; Yong Xu; Hongmei Wang; Ping Wang; Xuemin Wu (Journal of Environmental Chemical Engineering, 2023)

Developing effective radio frequency and ultraviolet combination technology based on evaluating quality characteristics of buckwheat - Juanjuan Xu; Liumin Fan; Dingting Zhou; Gaoji Yang; Xiangyu Guan; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2023)

Developing radio frequency pretreatment technology for improving yield and quality of flaxseed oil extractions - Liumin Fan; Juanjuan Xu; Xiangyu Guan; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2023)

Antibacterial mechanism of taxifolin and its application in milk preservation - Dan Yang; Rui Zhu; Hai-Xia Xu; Qing-Feng Zhang (Food Bioscience, 2023)

Use of nano titanium hydroxide and nano zirconium hydroxide fixed filter paper for rapid detection of Staphylococcus aureus in dairy products by PCR without pre-enrichment - Chun Wang; Ruohong Zhang; Xiaofang Wang; Rui Xu; Hejing Yan; Xiaoran Li; Shaojun Liu; Shuren Yin; Hong Yao; Yang Yang; Shenghui Cui; Yunchang Guo (Food Control, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Rapid identification of high and low cadmium (Cd) accumulating rice cultivars using machine learning models with molecular markers and soil Cd levels as input data - Zhong Tang; Ting-Ting You; Ya-Fang Li; Zhi-Xian Tang; Miao-Qing Bao; Ge Dong; Zhong-Rui Xu; Peng Wang; Fang-Jie Zhao (Environmental Pollution, 2023)

Spatio-temporal effects of urbanization on CO2 emissions: Evidences from 268 Chinese cities - Jiajun Xu; Jinchao Wang; Rui Li; Xiaojun Yang (Energy Policy, 2023)

Immunoregulatory hydrogel decorated with Tannic acid/Ferric ion accelerates diabetic wound healing via regulating Macrophage polarization - Na Xu; Yuanping Gao; Zheng Li; Yu Chen; Menglong Liu; Jiezhi Jia; Rui Zeng; Gaoxing Luo; Jiangfeng Li; Yunlong Yu (Chemical Engineering Journal, 2023)

Excited-state intramolecular proton transfer emitter for efficient violet-blue organic light-emitting diodes with hybridized local/charge transfer channel - Yibing Wu; Rongxin Wang; Rui Lin; Xuee Xu; Xingye Zhang; Osamah Alsalman; Yu Qiu; Ashraf Uddin; Xinhua Ouyang (Chemical Engineering Journal, 2023)

FHB resistance conferred by Fhb1 is under inhibitory regulation of two genetic loci in wheat (Triticum aestivum L.) - Guoqiang Li; Yang Yuan; Jiyang Zhou; Rui Cheng; Ruitong Chen; Xianmin Luo; Jinxing Shi; Heyu Wang; Boyang Xu; Youyu Duan; Jinkun Zhong; Xin Wang; et al. (Theoretical and Applied Genetics, 2023)

Correction to: Inhibition of mGluR5 alters BDNF/TrkB and GLT‑1 expression in the prefrontal cortex and hippocampus and ameliorates PTSD‑like behavior in rats - Shuyue Cheng; Jingjing Xu; Wei Wang; Rui Wang; Haonan Li; Zhijun Jiang; Dexiang Liu; Fang Pan (Psychopharmacology, 2023)

Design, synthesis and mechanism study of novel natural-derived isoquinoline derivatives as antifungal agents - Wei Chen; Rui Zhang; Yang Chen; Pingbing Yu; Yuxin Lan; Haojian Xu; Simin Lei (Molecular Diversity, 2023)

The role of Nod-like receptor protein 3 inflammasome activated by ion channels in multiple diseases - Xiaolin Xu; Xianli Wu; Gengyu Yue; Qimin An; Jun Lou; Xiaoxu Yang; Zhe Jin; Jianhong Ding; Yanxia Hu; Qian Du; Jingyu Xu; Rui Xie (Molecular and Cellular Biochemistry, 2023)
The inflammasome is a multimeric protein complex located in the cytoplasm that is activated by many factors and subsequently promotes the release of proinflammatory factors such as interleukin (IL)-1β and IL-18, resulting in a series of inflammatory responses that ultimately lead to the occurrence of various diseases. The Nod-like receptor protein 3 (NLRP3) inflammasome is the most characteristic type and the most widely studied among many inflammasomes. Activation of the NLRP3 inflammasome is closely related to the occurrence of many diseases, such as Alzheimer's disease. At present, a large number of studies have focused on the mechanisms underlying the activation of the NLRP3 inflammasome. Plenty of articles have reported the activation of the NLRP3 inflammasome by various ions, such as K + and Na + reflux and Ca 2+ influx. However, few articles have reviewed the effects of various ion channels on the activation of the NLRP3 inflammasome and the relationship between the diseases caused by these proteins. This article mainly summarizes the relationship between intracellular and extracellular ion activities and ion channels and the activation of the NLRP3 inflammasome. We also provide a general summary of the diseases of each system caused by NLRP3 activation. We hope that more research will provide options for the treatment of diseases driven by the NLRP3 inflammasome.

New methylene blue-mediated photodynamic inactivation of multidrug-resistant Fonsecaea nubica infected chromoblastomycosis in vitro - Mengxue Zheng; Xiaoqing Zhou; Jiayin Pang; Zengjun Yang; Yongzhen Zou; Lian Zhang; Yan Xu; Rui Yin (Brazilian Journal of Microbiology, 2023)

Rhizospheric soil organic carbon accumulated but its molecular groups redistributed via rhizospheric soil microorganisms along multi-root Cerasus humilis plantation chronosequence at the karst rocky desertification control area - Qin Tang; Qiang Li; Lingchen Tong; Rui Wu; Jiao Xu (Environmental Science and Pollution Research, 2023)

In-situ preparation of yeast-supported Fe0@Fe2O3 as peroxymonosulfate activator for enhanced degradation of tetracycline hydrochloride - Bin Li; Chen-Xuan Li; Yan Wang; Weiyi Xu; Kangping Cui; Xinyuan Zhan; Rui Deng; Xing Zhang (Chemosphere, 2023)

Sources and historical records of metal(loid)s in river sediments from an agricultural tributary of Tuojiang river: Evidence from geochemical analyses and Pb isotope - Fen Xu; Rui Yang; Hong Wang; Xiaoxia He; Weiwei Li; Yao Wei; Linlin Bao; Jianfei Yuan; Hongjin Tong (Chemosphere, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

CuFe2O4/diatomite actuates peroxymonosulfate activation process: Mechanism for active species transformation and pesticide degradation - Peng Xu; Rui Wei; Peng Wang; Xiang Li; Chunyan Yang; Tianyao Shen; Tong Zheng; Guangshan Zhang (Water Research, 2023)

Associations between summer wind environment and urban physical indicators in commercial blocks based on field measurement and simulation in Xi'an - Qian Zhang; Rui Dong; Duo Xu; Dian Zhou; Alessandro Rogora (Urban Climate, 2023)

A deep leaning method for dynamic vibration analysis of bridges subjected to uniform seismic excitation - Rui Yi; Xiaoyu Li; Siyu Zhu; Yongle Li; Xinyu Xu (Soil Dynamics and Earthquake Engineering, 2023)

Integrative effects of microbial inoculation and amendments on improved crop safety in industrial soils co-contaminated with organic and inorganic pollutants - Xiaowei Cui; Xiufeng Cao; Wenxiu Xue; Lei Xu; Zhaojie Cui; Rui Zhao; Shou-Qing Ni (Science of The Total Environment, 2023)

Effects of saline-alkali stress on the tissue structure, antioxidation, immunocompetence and metabolomics of Eriocheir sinensis - Rui Zhang; Zhigang Zhao; Mingshuai Li; Liang Luo; Shihui Wang; Kun Guo; Wei Xu (Science of The Total Environment, 2023)

Migration, solidification/stabilization mechanism of heavy metal in lightweight ceramisite from co-sintering fly ash and electrolytic manganese residue - Xinyuan Zhan; Yan Wang; Li’ao Wang; Chenxuan Li; Xiaowei Xu; Rui Deng (Process Safety and Environmental Protection, 2023)

Diversity and distribution variation of urban spontaneous vegetation with distinct frequencies along river corridors in a fast-growing city - Xiaopeng Li; Sining Zhang; Rui Huang; Li Feng; Sihui Xu; Baichuan Liu (Journal of Environmental Management, 2023)

Wide-Scope Multi-residue analysis of pesticides in beef by gas chromatography coupled with quadrupole Orbitrap mass spectrometry - Xu Pang; Jing Qiu; Zhaoyang Zhang; Pi Li; Jiangtao Xing; Xin Su; Guiqiao Liu; Changyuan Yu; Rui Weng (Food Chemistry, 2023)

Combined methods elucidate the multi-organ toxicity of cylindrospermopsin (CYN) on Daphnia magna - Zhongshi He; Youxin Chen; Da Huo; Jin Gao; Yewei Xu; Rui Yang; Yiming Yang; Gongliang Yu (Environmental Pollution, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Increased hypertension risk for the elderly with high blood levels of strontium and lead - Jiebao Zhang; Chunfang Xu; Yan Guo; Xingyi Jin; Zi Cheng; Qi Tao; Lin Liu; Rui Zhan; Xuemin Yu; Hongjuan Cao; Fangbiao Tao; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

In situ degradation of fluoroquinolone antibiotics in groundwater by CoFe2O4 nanoparticle-activated peroxymonosulfate: Performance, activation mechanism, degradation pathway - Rui Xu; Kun Qian; Xianjun Xie; Jiangjun Chen; Weiguo Tang; Feng Tao; Yanxin Wang (Applied Geochemistry, 2023)

Diversity of Fusarium community assembly shapes mycotoxin accumulation of diseased wheat heads - Qiang Wang; Rui Song; Sanhong Fan; Jeffrey J. Coleman; Xiangming Xu; Xiaoping Hu (Molecular Ecology, 2023)
Fusarium head blight (FHB) is a major disease worldwide on cultivated cereals, caused by several Fusarium species. FHB can cause not only yield reduction but also accumulation of mycotoxins in the grain contaminating the food supply. Much of the earlier research has focused on Fusarium pathogenesis, conditions required for disease development and toxin accumulation, and FHB management. However, the Fusarium community composition within the micro‐habitat of a single diseased wheat head in the field has had limited investigation. Similarly, the relationship between the Fusarium community structure and mycotoxin accumulation within diseased heads remains unclear. In the present study, we investigated the Fusarium community in diseased heads sampled from different geographical sites in China. Several sites in Shandong province formed a transitional region which contained highly variable profiles of Fusarium OTUs, where a single diseased head could contain more than 10 Fusarium OTUs. Mycotoxin accumulation was independent of geographical properties, however, deoxynivalenol, 15‐acetyldeoxynivalenol and zearalenone concentrations showed a significant negative correlation with Fusarium diversity on diseased heads while a significant positive correlation between nivalenol concentration and Fusarium diversity was observed. Taken together, the Fusarium OTU diversity within diseased heads in the field significantly influences mycotoxin accumulation, providing an important point to consider in FHB disease management and mycotoxin research.

Canopy height, rather than neighborhood effects, shapes leaf herbivory in a tropical rainforest - Shuang Zhang; Guo‐Rui Xu; Yu‐Xin Zhang; Wen‐Fu Zhang; Min Cao (Ecology, 2023)
Factors shaping the interspecific variations in herbivory have puzzled ecologists for decades and several hypotheses have been proposed to explain interspecific variation in leaf herbivory. In a tropical rainforest in Yunnan Province, China, we collected 6732 leaves from 129 species with canopy heights ranging from 1.6 to 65.0 m above the ground. We tested the role of canopy height, the diversity, composition and structural heterogeneity of neighbors and leaf traits in shaping the interspecific variations in herbivory. Results show that leaf herbivory decreased with canopy height and specific leaf area (SLA) and increased with leaf size. However, neighboring species' diversity, composition, and structural heterogeneity showed no association with herbivory. Therefore, neither the visual apparency effect nor the associational resistance effect was detected in this hyperdiverse tropical rainforest. These findings highlight the importance of vertical structure in shaping herbivory patterns in natural communities.

A systematic knowledge pedigree analysis on green governance - Rui Yang; Yingwen Chen; Jie Zhong; Yujin Xu; Xin An (Environment, Development and Sustainability, 2023)

Recent advances in CO2 fixation by microalgae and its potential contribution to carbon neutrality - Peilun Xu; Jun Li; Jun Qian; Bang Wang; Jin Liu; Rui Xu; Paul Chen; Wenguang Zhou (Chemosphere, 2023)

Evaluation method of rowing performance and its optimization for UAV-based shot seeding device on rice sowing - Wei Liu; Zhiyan Zhou; Xuelang Xu; Qingyu Gu; Shuaishuai Zou; Weizhuo He; Xiwen Luo; Junhao Huang; Jianqin Lin; Rui Jiang (Computers and Electronics in Agriculture, 2023)

The effect of repeated energy inputs on the release profiles of extracellular organic substances in sewage sludge - Rui Liu; Ying Xu; Liang Song; Shiyu Liu; Zixuan Liang; Danyang Zhu; Xiaohu Dai (Water Research, 2023)

Interpretable machine learning assisted spectroscopy for fast characterization of biomass and waste - Rui Liang; Chao Chen; Tingxuan Sun; Junyu Tao; Xiaoling Hao; Yude Gu; Yaru Xu; Beibei Yan; Guanyi Chen (Waste Management, 2023)

Regulation of denitrification performance and microbial topology by lights: Insight into wavelength effects towards microbiota - Yang Liao; Jiyong Bian; Shiyu Miao; Siqi Xu; Rui Li; Ruiping Liu; Huijuan Liu; Jiuhui Qu (Water Research, 2023)

Post COVID-19 pandemic recovery of intracity human mobility in Wuhan: Spatiotemporal characteristic and driving mechanism - Rui An; Zhaomin Tong; Xiaoyan Liu; Bo Tan; Qiangqiang Xiong; Huixin Pang; Yaolin Liu; Gang Xu (Travel Behaviour and Society, 2023)

Helper objective-based multifactorial evolutionary algorithm for continuous optimization - Xu Yang; Wenhua Li; Rui Wang; Kang Yang (Swarm and Evolutionary Computation, 2023)

Stochastic dynamic response and seismic fragility analysis for high concrete face rockfill dams considering earthquake and parameter uncertainties - Kehao Chen; Rui Pang; Bin Xu (Soil Dynamics and Earthquake Engineering, 2023)

Association between exposure to ambient air pollution and semen quality: A systematic review and meta-analysis - Ruijun Xu; Yanling Zhong; Rui Li; Yingxin Li; Zihua Zhong; Tingting Liu; Qiling Wang; Ziquan Lv; Suli Huang; Yong-Gang Duan; Xinzong Zhang; Yuewei Liu (Science of The Total Environment, 2023)

Atmospheric microplastics at a southern China metropolis: Occurrence, deposition flux, exposure risk and washout effect of rainfall - Zhen Yuan; Chenglei Pei; Hengxiang Li; Lang Lin; Shan Liu; Rui Hou; Ran Liao; Xiangrong Xu (Science of The Total Environment, 2023)

Comparative studies of transformation behaviors and mechanisms of halophenols in multiple chemical oxidative systems - Xiaoxue Pan; Junyan Wei; Min Wang; Jie Zhang; Zhiming Xu; Haojie Wei; Nami Lai; Kainan Nian; Rui Zhang; Xuesheng Zhang (Science of The Total Environment, 2023)

Immunotherapy in gastrointestinal cancers: advances, challenges, and countermeasures - Zi-Xian Wang; Yi-Qian Pan; Xuexin Li; Takeshi Tsubata; Rui-Hua Xu (Science Bulletin, 2023)

Future land-use change and its impact on terrestrial ecosystem carbon pool evolution along the Silk Road under SDG scenarios - Min Cao; Ya Tian; Kai Wu; Min Chen; Yu Chen; Xue Hu; Zhongchang Sun; Lijun Zuo; Jian Lin; Lei Luo; Rui Zhu; Zhenci Xu; et al. (Science Bulletin, 2023)

Characteristics of silicon and phytolith distribution in bamboo (Ferrocalamus strictus): variations between different organs and ages - Rui Xu; Honglan He; Huijun Guo; Fangwei Zhu; Shuguang Wang; Cefeng Dai; Xiaofeng Zheng; Dongbo Xie; Haoming Li; Changming Wang; Hui Zhan (Review of Palaeobotany and Palynology, 2023)

JA-induced TaMPK6 enhanced the freeze tolerance of Arabidopsis thaliana through regulation of ICE-CBF-COR module and antioxidant enzyme system - Meng-Meng Yu; Rui Wang; Jing-Qiu Xia; Chang Li; Qing-Hua Xu; Jing Cang; Yu-Ying Wang; Da Zhang (Plant Science, 2023)

Origin of biotite-rich xenoliths in the Eocene Beiya porphyry: Implications for upper-crustal Au remobilization and formation of giant porphyry Au systems in a collisional setting - Ye Zhou; Zengqian Hou; Rui Wang; Bo Xu; Noreen J. Evans; Wenyan He; Yuanchuan Zheng; Jiaxi Zhou (Lithos, 2023)

Magnetic field assisted enhancement of electronic metal-support interactions in FexCuy@TiO2-δ catalysts for arsine catalytic oxidation - Yibing Xie; Xueqian Wang; Ping Ning; Langlang Wang; Yixing Ma; Yuan Li; Rui Cao; Hui Zhang; Xiang Li; Bowen Xu (Journal of Cleaner Production, 2023)

Environmental risk of tailings pond leachate pollution: Traceable strategy for leakage channel and influence range of leachate - Bowen Shi; Xixi Li; Weiwu Hu; Beidou Xi; Shengrong Liu; Di Liu; Congchao Xu; Zihao Jia; Rui Li (Journal of Environmental Management, 2023)

Crushing combined with high–frequency turning can promote material degradation of sheep manure compost on the Qinghai–Tibet Plateau by improving the microbial metabolic function - Rui Cai; Xinyu Cui; Xiaohui Cao; Xin Jiang; Rongze Wang; Chuncheng Xu (Journal of Environmental Chemical Engineering, 2023)

Large-scale mapping of solifluction terraces in the southeastern Tibetan Plateau using high-resolution satellite images and deep learning - Ronggang Huang; Liming Jiang; Zhida Xu; Rui Guo; Fujun Niu; Hansheng Wang (Geomorphology, 2023)

Investigation of the synergetic regulation of O2/Ar preheating treatment and sodium salt addition on semichar combustion characteristics - Lei Zhang; Wenkun Zhu; Zhuozhi Wang; Mengfan Yuan; Xingyi Wang; Xu Yang; Rui Sun (Fuel, 2023)

Corrigendum to “Self-supported PdNi dendrite on Ni foam for improving monohydric alcohol and polyhydric alcohols electrooxidation” [Fuel 326 (2022) 125083] - Ning Zhang; Jing Wang; Wen Zhang; Yingxiu Zhao; Zemeng Dong; Zexing Wu; Guang-Rui Xu; Lei Wang (Fuel, 2023)

The effect of clay type and solid wettability on bitumen extraction from Canadian oil sands - An Li; Rui Li; Ci Yan; Han Wang; Qingxia Liu; Jacob H. Masliyah; Hongbo Zeng; Zhenghe Xu (Fuel, 2023)

Fabrication of starch-based emulsion gel beads by an inverse gelation technique for loading proanthocyanidin and curcumin - Xiaotong Bu; Minghang Guan; Lei Dai; Na Ji; Yang Qin; Xingfeng Xu; Liu Xiong; Rui Shi; Qingjie Sun (Food Hydrocolloids, 2023)

Inhibition of human sulfotransferases (SULTs) by per- and polyfluoroalkyl substances (PFASs) and structure-activity relationship - Yong-Zhe Liu; Kai Yang; Wei Zhang; Qian zhang; Tong-Feng Liu; Tong Xu; Yang Li; Rui-Xue Ran; Kun Yang; Yun-Feng Cao; Zhong-Ze Fang (Food and Chemical Toxicology, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Long-term exposure to fine particulate matter and site-specific cancer mortality: A difference-in-differences analysis in Jiangsu province, China - Zhaoyu Fan; Yingxin Li; Jing Wei; Gongbo Chen; Rui Wang; Ruijun Xu; Tingting Liu; Ziquan Lv; Suli Huang; Hong Sun; Yuewei Liu (Environmental Research, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

Modeling and prediction of short/long term mechanical behavior of FRP-strengthened slabs using innovative composite finite elements - Rui Wu; Rongqiao Xu; Guannan Wang (Engineering Structures, 2023)

Cl modulation on boron-rich carbon embedded with NiFe alloys for efficient oxygen evolution reaction - Jiateng Li; Kaitian Zheng; Chi Zhang; Long Jiao; Zhiheng Dong; Xinyue Tao; Rui Su; Haijiao Xie; Chunjian Xu (Chemical Engineering Journal, 2023)

A pH/cellulase dual stimuli-responsive cellulose-coated metal–organic framework for eco-friendly fungicide delivery - Yingjian Ma; Meng Yu; Yinmin Wang; Shouhe Pan; Xuelin Sun; Rui Zhao; Zhe Sun; Rui Gao; Xinyu Guo; Yong Xu; Xuemin Wu (Chemical Engineering Journal, 2023)

C3-symmetric trimeric imidazole naphthoquinone derivative with dual redox-active sites for high-performance cathodic lithium storage - Yifang Zhu; Wei Jin; Haiguang Gao; Yanli Chen; Tai-Rui Wu; De-Yin Wu; Yucheng Huang; Dengfeng Guo; Zhidong Chen; Qinghong Huang; Jianyu Cao; Juan Xu (Chemical Engineering Journal, 2023)

High adaptability and stability FeCo2O4/diatomite composite for efficient peroxymonosulfate activation: Performance, water matrix impact, and mechanism - Peng Xu; Xiang Li; Rui Wei; Chunyan Yang; Tianyao Shen; Peng Wang; Guangshan Zhang (Chemical Engineering Journal, 2023)

Ultra-thin hierarchical porous carbon coated metal phosphide self-assembled efficient tri-functional electrodes for overall water splitting and rechargeable zinc-air batteries - Rui He; Tuo Lu; Nengneng Xu; Guicheng Liu; Yanxing Zhang; Jinli Qiao (Chemical Engineering Journal, 2023)

π-Conjugated N-heterocyclic compound with redox-active quinone and pyrazine moieties as a high-capacity organic cathode for aqueous zinc-ion batteries - Yanjun Shi; Pengcheng Wang; Haiguang Gao; Wei Jin; Yanli Chen; Yucheng Huang; Tai-Rui Wu; De-Yin Wu; Juan Xu; Jianyu Cao (Chemical Engineering Journal, 2023)

Magnetic hydrochar derived from waste lignin for thallium removal from wastewater: Performance and mechanisms - Huabin Wang; Ran Duan; Lin Ding; Lin Tian; Ying Liu; Yong Zhang; Rui Xu (Bioresource Technology, 2023)

Comparison and Investigation of Exosomes from Human Amniotic Fluid Stem Cells and Human Breast Milk in Alleviating Neonatal Necrotizing Enterocolitis - Xiaohan Hu; Rui Zhang; Hansi Liang; Jingnan An; Yuan Yang; Jie Huo; Zhenjiang Chen; Wei Quan; Lu Jiang; Cancan Li; Jian Li; Fang Li; et al. (Stem Cell Reviews and Reports, 2023)
In view of the devastating impact of neonatal necrotizing enterocolitis (NEC) on newborns, the research on its intervention is particularly important. Although exosomes from human amniotic fluid stem cells (AFSC) and human breast milk (HBM) can protect against NEC, their mechanisms remain unclear. Here, we intend to compare the intervention effects of two types of exosomes on NEC mouse model and reveal their respective regulatory mechanisms. In general, both AFSC-derived exosomes (AFSC-exos) and HBM-derived exosomes (HBM- exos) can alleviate NEC- associated intestinal injury, significantly reduce NEC score, and reduce systemic and ileal inflammation and NEC related brain injury during experimental NEC. However, the mode and mechanism of action of the two sources of exosomes were not identical. In vivo, the number of ileal crypts was more significantly restored after HBM-exos intervention than AFSC-exos, and in vitro, HBM-exos preferentially inhibited the inflammatory response of intestinal epithelial cells (IECs), whereas AFSC-exos preferentially regulated the migration of IECs. Mechanistically, GO and KEGG analyses revealed the different therapeutic mechanisms of AFSC-exos and HBM-exos in NEC. Taken together, our results illustrate that AFSC-exos and HBM-exos reduce the severity of experimental NEC and intestinal damage through different mechanisms, supporting the potential of cell-free or breast milk free exosome therapy for NEC. Graphical Abstract

Inhibition of mGluR5 alters BDNF/TrkB and GLT-1 expression in the prefrontal cortex and hippocampus and ameliorates PTSD-like behavior in rats - Shuyue Cheng; Jingjing Xu; Wei Wang; Rui Wang; Haonan Li; Zhijun Jiang; Dexiang Liu; Fang Pan (Psychopharmacology, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Repetitive transcranial magnetic stimulation enhances the neuronal excitability of mice by regulating dynamic characteristics of Granule cells’ Ion channels - Haijun Zhu; Xiaonan Yin; Huilan Yang; Rui Fu; Wentao Hou; Chong Ding; Guizhi Xu (Cognitive Neurodynamics, 2023)

Energy and environmental performance evaluation of China's non-ferrous metals industry from the perspective of network structure - Rui Yang; Yujin Xu; Kaiyuan Liu (Clean Technologies and Environmental Policy, 2023)

Sandstorms damage the photosynthetic activities of Haloxylon ammodendron seedlings - Shengbo Shi; Dangwei Zhou; Rui Shi; Tao Sun; Fanglin Wang; Xiuzhen Gao; Yunian Zhang; Peng Zhao; Gaoxing Xu; Jinnian Tang (Acta Physiologiae Plantarum, 2023)
Haloxylon ammodendron is a preferred shrub species for buffering against wind and fixing sand in arid sandy areas of northwest China. To determine whether sandstorms cause damage to H. ammodendron seedlings, we investigated the effects of wind-blown sands on the photosynthetic function of H. ammodendron by simulating sand-carrying wind in the wind tunnel. The results showed that photosystem II (PSII) non-photochemical quenching ( NPQ ) was sensitive to wind erosion, and sustained blowing of sand-carrying winds enhanced NPQ reduction. The rapidly relaxing quenching NPQ f made up the majority component of NPQ ; the NPQ f / NPQ ratio was approximately 64.4% in the sand-free wind group and nearly 56.2% in the sand-carrying wind group. The distribution of the quantum efficiency of the excitation energy indicated that the relative proportions of the quantum yield of PSII photochemistry Φ PSII , the quantum yield of quenching due to light-induced Φ NPQ , and non-light-induced Φ NO were influenced by both wind erosion and light intensity; the sand-carrying wind resulted in a relative decrease in Φ NPQ and a corresponding increase in Φ NO . The maximum quantum efficiency of PSII photochemistry F v / F m was relatively stable in the sand-free wind group, with an average value of approximately 0.81. Compared to sand-free wind, sand-carrying winds caused remarkable decreases in F v / F m . Light intensity was the main factor affecting Φ PSII , Φ NPQ , and relative electron transport rate ( rETR ); there was no interaction effect between the duration of sand-carrying wind and light intensity. Taken together, wind-blown sands cause irreversible damage to the photosynthesis of H. ammodendron seedlings, which is the main factor restricting population regeneration in shelterbelts.

Species of fast bulk‐soil nutrient cycling have lower rhizosphere effects: A nutrient spectrum of rhizosphere effects - Lijuan Sun; Yuki Tsujii; Tianle Xu; Mengguang Han; Rui Li; Yunfeng Han; Dayong Gan; Biao Zhu (Ecology, 2023)
Tree roots not only acquire readily‐usable soil nutrients but also affect microbial decomposition and manipulate nutrient availability in their surrounding soils, that is, rhizosphere effects (REs). Thus, REs challenge the basic understanding of how plants adapt to the environment and co‐exist with other species. Yet, how REs vary among species in response to species‐specific bulk soil nutrient cycling is not well‐known. Here, we studied how plant‐controlled microbial decomposition activities in rhizosphere soils respond to those in their corresponding bulk soils and whether these relations depend on species‐specific nutrient cycling in the bulk soils. We targeted 55 woody species of different clades and mycorrhizal types in three contrasting biomes, namely a temperate forest, a subtropical forest, and a tropical forest. We found that microbial decomposition activities in rhizosphere soils responded linearly to those in their corresponding bulk soils at the species level. Thereafter, we found that REs (parameters in rhizosphere soils minus those in corresponding bulk soils) of microbial decomposition activities had negative linear correlations with microbial decomposition activities in corresponding bulk soils. A multiple factor analysis revealed that soil organic carbon, total nitrogen, and soil water content favored bulk soil decomposition activities in all three biomes, showing that the magnitude of REs varied along a fast‐slow nutrient cycling spectrum in bulk soils. The species of fast nutrient cycling in their bulk soils tended to have smaller or even negative REs. Therefore, woody plants commonly utilize both positive and negative REs as a nutrient‐acquisition strategy. Based on the trade‐offs between REs and other nutrient‐acquisition strategies, we proposed a push and pull conceptual model which can bring plant nutrient‐acquisition cost and plant carbon economics spectrum together in the future. This model will facilitate not only the carbon and nutrient cycling but also the mechanisms of species co‐existence in forest ecosystems.

Molecular identification of an insulin-like peptide from the swimming crab Portunus trituberculatus and evidence for its glucoregulation function - Rui Xu; Meng-en Wang; Shisheng Tu; Xi Xie; Dongfa Zhu (Frontiers in Marine Science, 2023)
Insulin-like peptides (ILPs) are essential to the animal kingdom for regulating growth and development, reproduction, behavior, metabolism, and lifespan. In crustaceans, the most well-known ILP is insulin-like androgenic gland hormone, a key hormone in regulating sex differentiation and reproduction. Identification of other ILPs and their functions are still limited. In this study, an insulin-like peptide gene of the swimming crab Portunus trituberculatus was cloned and characterized. Its transcripts were mainly found in nerve tissues and expression could be induced by glucose, implying a putative role in glucoregulation. After depletion of endogenous ILP, injection of ILP dsRNA (dsILP) significantly elevated blood glucose levels and recombinant ILP (rILP) decreased hemolymph glucose levels, further clarifying the involvement of acquired ILP in hemolymph glucose regulation. Injection of dsILP decreased PtAkt , PtGS , PtPFK and increased PtGSK and PtPEPCK gene expression. The opposite profile was observed after glucose and rILP injection, indicating that PtILP might negatively regulate hemolymph glucose levels via the IIS (insulin/IGF-1 signaling) pathway by inhibiting gluconeogenesis and promoting glycogen synthesis and glycolysis. This study has refined the mechanism of glucose regulation in crustaceans and laid the foundation for further studies on ILP function.

Diffusion simulation and risk assessment model establishment of chlorine gas leakage based on terrain conditions - Xiao-ting Ren; Xiao-ling Ma; Jiang-zheng Liu; Rui Liu; Chen-qian Zhao; Hao Wu; Zhao Wang; Chun-xu Hai; Xiao-di Zhang (Environmental Science and Pollution Research, 2023)

Particle sorting to improve the removal of fluoride and aluminum nitride from secondary aluminum dross by roasting - Huimin Xie; Zhaohui Guo; Rui Xu; Yanglin Zhang (Environmental Science and Pollution Research, 2023)

Tailoring enzymatic loading capacity on CdS nanorods@ZnIn2S4 nanosheets 1D/2D heterojunctions: Toward ultrasensitive photoelectrochemical bioassay of tobramycin - Rui Hu; Ben-Fang Xu; Yadong Xue; Zhi-Zhi Xu; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemosphere, 2023)

Sodium acetate alleviates adverse effects caused by the diet with high proportion of soybean meal in turbot (Scophthalmus maximus L.) - Wentao Wang; Jinjin Zhang; Rui Shao; Shufei Liang; Hui Zhang; Weiqi Xu; Mingzhu Li; Qinghui Ai; Kangsen Mai; Min Wan (Aquaculture, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Modelling air conductivity function of unsaturated root-permeated soil - Rui Chen; Jun-Wen Huang; Anthony Kwan Leung; Zhong-Kui Chen; Yang Ping; Ying Xu (Soil and Tillage Research, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

Trophoblast-specific knockdown of CSPG4 expression causes pregnancy complications with poor placentation in mice - Junfei Xu; Anwen Yuan; Rui Su; Qing Yang; Xiujun Fan; Juzuo Zhang (Reproductive Biology, 2023)

‘Yunnan’ quince rootstock promoted flower bud formation of ‘Abbé Fetel’ pear by altering hormone levels and PbAGL9 expression - Liu Cong; Hutian Ling; Shanshan Liu; Azheng Wang; Rui Zhai; Chengquan Yang; Zhigang Wang; Lingfei Xu (Journal of Plant Physiology, 2023)

Interaction of permafrost degradation and thermokarst lakes in the Qinghai–Tibet Plateau - Zhida Xu; Liming Jiang; Rui Guo; Ronggang Huang; Zhiwei Zhou; Fujun Niu; Zhiping Jiao (Geomorphology, 2023)

Detecting ionizing radiation dose using composite hydrogel-based sensors - Li Jiang; Chengfang Zhang; Xinyue Xu; Rui Hu; Ping Zhang; Rensheng Wang; Xinjian Chen; Liang Hu (Chemical Engineering Journal, 2023)

Novel in-situ deposited V2O5 nanorods array film sensor with enhanced gas sensing performance to n-butylamine - Xuemei Sun; Rui Gao; Yuanyuan Wu; Xianfa Zhang; Xiaoli Cheng; Shan Gao; Yingming Xu; Lihua Huo (Chemical Engineering Journal, 2023)

Slab dehydration and magmatism in the Kurile arc as a function of depth: An investigation based on B-Sr-Nd-Hf isotopes - Hong-Yan Li; Chao Xie; Jeffrey G. Ryan; Chuan-Mao Yang; Rui-Peng Zhao; Chao Zhang; Yi-Gang Xu (Chemical Geology, 2023)

Morphology and location of sensilla in the antennae and ovipositor of Sirex noctilio (Hymenoptera: Siricidae) - Enhua Hao; Rui Liu; Ruirui Xu; Pengfei Lu; Haili Qiao (Arthropod Structure & Development, 2023)

The circadian regulation of extracellular ATP - Xin Wang; Yu-Ting Dong; Xiu-Ming Hu; Ji-Zhou Zhang; Nan-Rui Shi; Yan-Qin Zuo; Xu Wang (Purinergic Signalling, 2023)
Extracellular ATP is a potent signaling molecule released from various cells throughout the body and is intimately involved in the pathophysiological functions of the nervous system and immune system by activating P2 purinergic receptors. Recent increasingly studies showed that extracellular ATP exhibits circadian oscillation with an approximately 24-h periodicity, which participates in regulatory pathways of central oscillator suprachiasmatic nucleus and peripheral oscillator bladder, respectively. Oscillators modulate the protein expression of ATP release channels and ectonucleotidase activity through clock genes; indeed, real-time alterations of ATP release and degradation determine outcomes of temporal character on extracellular ATP rhythm. The regulatory pathways on extracellular ATP rhythm are different in central and peripheral systems. In this review, we summarize the circadian rhythm of extracellular ATP and discuss several circadian regulatory pathways in different organs via ATP release and degradation, to provide a new understanding for purinergic signaling in the regulatory mechanism of circadian rhythm and a potential target to research the circadian regulation of extracellular ATP in other circadian oscillators.

Tet Enzyme-Mediated Response in Environmental Stress and Stress-Related Psychiatric Diseases - Meiling Xia; Rui Yan; Myoung-Hwan Kim; Xingshun Xu (Molecular Neurobiology, 2023)

Effects of Alpine Grassland Degradation on Soil Microbial Communities in Qilian Mountains of China - Chunming Li; Derong Zhang; Gengchun Xu; Rui Yan; Yang Huang; Liuqing Feng; Jin Yi; Xiangyu Xue; Huixia Liu (Journal of Soil Science and Plant Nutrition, 2023)

Quantitative estimation of bubble volume fraction of submarine seep plumes by modeling seismic oceanography data - Tonggang Han; Jiangxin Chen; Leonardo Azevedo; Bingshou He; Huaning Xu; Rui Yang (Journal of Oceanology and Limnology, 2023)

rTFPI Protects Cardiomyocytes from Hypoxia/Reoxygenation Injury through Inhibiting Autophagy and the Class III PI3K/Beclin-1 Pathway - Runan Yan; Wei Gao; Wenjia Chen; Yue Liu; Li Shen; Yue Dai; Rui Xu; Qing Chang; Yu Fu; Yong Zhao (Cell Biochemistry and Biophysics, 2023)

Combined effects of fluoroquinolone antibiotics and organophosphate flame retardants on Microcystis aeruginosa - Yang Zhao; Yingping Huang; Shuang Hu; Tao Xu; Yanfen Fang; Huigang Liu; Ying Xi; Rui Qu (Environmental Science and Pollution Research, 2023)

Spatiotemporal difference of leachate production and its impact on the development and dynamics of LCS clogging - Ya Xu; Guangyuan Yao; Rui Xiang; Yuqiang Liu; Qifei Huang (Waste Management, 2023)

Disabled travel and urban environment: A literature review - Xiaoming Shen; Siqi Zheng; Rui Wang; Qinwei Li; Zike Xu; Xiaoliang Wang; Jiayu Wu (Transportation Research Part D: Transport and Environment, 2023)

Kidney Mesenchymal stem cells alleviate cisplatin-induced kidney injury and apoptosis in rats - Rui-ning Liang; De-qi Yan; Xing-ping Zhang; Xu Chen; Wen-hui Zhang; Hong-lin Jia (Tissue and Cell, 2023)

SLP-2 regulates the generation of reactive oxygen species and the ERK pathway to promote papillary thyroid carcinoma motility and angiogenesis - Jianping Chen; Duting Wang; Rui Xu; Ting Yao; Yu Guo; Qi Liu; Erlong Yang; Zhengqing Wu; Zhenyu Xu (Tissue and Cell, 2023)

Seismic collaborative reliability evaluation of slopes using subset simulation via support vector machine - MingYang Xu; Yang Zhou; Rui Pang; Bin Xu (Soil Dynamics and Earthquake Engineering, 2023)

Role of humic substances and alkaline in phosphorus release from sludge pre-treated by (alkali-) hydrothermal - Xiaofeng Xu; Zexuan Du; Wei Mou; Rui Deng; Li Gu (Science of The Total Environment, 2023)

Manganese-induced α-synuclein overexpression promotes the accumulation of dysfunctional synaptic vesicles and hippocampal synaptotoxicity by suppressing Rab26-dependent autophagy in presynaptic neurons - Zhuo Ma; Kuan Liu; Rui-feng Zhang; Zi-xin Xie; Wei Liu; Yu Deng; Xin Li; Bin Xu (Science of The Total Environment, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

The effects of salt flow on the cross-section restoration of salt-bearing fold-and-thrust belts: An example from the Kuqa depression - Wanhui He; Wei Wang; Huiwen Xie; Hongwei Yin; Dong Jia; Zhenping Xu; Haoyu Luo; Rui Yuan (Journal of Structural Geology, 2023)

A global meta-analysis of coal mining studies provides insights into the hydrologic cycle at watershed scale - Jiahui Yang; Huaixin Wei; Zelin Quan; Rui Xu; Zhaohui Wang; Hailong He (Journal of Hydrology, 2023)

In situ preparation of a multifunctional adsorbent by optimizing the Fe2+/Fe3+/Mn2+/HA ratio for simultaneous and efficient removal of Cd(II), Pb(II), Cu(II), Zn(II), As(III), Sb(III), As(V) and Sb(V) from aqueous environment: Behaviors and mechanisms - Qian Li; Lang Liao; Rui Xu; Zhenguo Wu; Zhe Yin; Yuqi Han; Yan Zhang; Yongbin Yang; Tao Jiang (Journal of Hazardous Materials, 2023)

Self-assembly of Au nanocrystals into large-area 3-D ordered flexible superlattice nanostructures arrays for ultrasensitive trace multi-hazard detection - Wei Liu; Qian Li; Jiabin Wu; Weizhe Wang; Rui Jiang; Chunli Zhou; Shuangbao Wang; Xueming Zhang; Tangyou Sun; Zhimou Xu; Dingsheng Wang (Journal of Hazardous Materials, 2023)

Antifouling modification of PVDF membranes via incorporating positive-charge tuned quaternized chitosan magnetic particles - Ziming Zhu; Xuan Zhou; Rui Zhang; Yahong Li; Yuan Liu; Jianxian Zeng; Xiaoping Huang; Pengfei Liu; Jianrong Xue; Kaipeng Cheng; Hongfei Xu (Journal of Environmental Chemical Engineering, 2023)

Fire-resistant MXene composite aerogels for effective oil/water separation - Guixin Wang; Yuxin Xu; Rui Zhang; Shuang Gai; Ying Zhao; Fan Yang; Kui Cheng (Journal of Environmental Chemical Engineering, 2023)

Experimental and kinetic study on JP-10/air autoignition and the effect of NO2 at high temperatures - Lei Shi; Ping Xu; Rui Wang; Weixin Tang; Tao Ding; Rongpei Jiang; Changhua Zhang (Fuel, 2023)

Fast pyrolysis of algae model compounds for bio-oil: In-depth insights into the volatile interaction mechanisms based on DFT calculations - Donghua Xu; Junhao Lin; Rui Ma; Jiahui Hou; Shichang Sun; Ning Ma (Fuel, 2023)

Multiple strategies for high-efficiency expression of Thermomyces lanuginosus lipase in Pichia pastoris and production of biodiesel in solvent-free system - Rui Xu; Zirong Chen; Yanyang Chen; Xiaoyue Wang; Yu Zhang; Xun Li; Fei Wang (Fuel, 2023)

Expanded polystyrene buoys as an important source of hexabromocyclododecanes for aquatic ecosystem: Evidence from field exposure with different substrates - Yun-Feng Pan; Shan Liu; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Environmental Pollution, 2023)

Alleviative effects of astragaloside IV on cyclophosphamide-induced oxidative damage and immunosuppression in tilapia (Oreochromis niloticus) - Liping Cao; Jinliang Du; Rui Jia; Jiancao Gao; Zhijuan Nie; Nailin Shao; Quanjie Li; Haojun Zhu; Guojun Yin; Weidong Ding; Gangchun Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Manipulate the acidity of gallium doped Silicalite-1 to optimize methanol to propene performance - Ling Zhang; Rui Tu; Guoqing Ren; Zhen Li; Shengliang Zhai; Yuchun Xu; Tie Yu (Chemical Engineering Journal, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Facile fabrication of flexible and ultrathin self-assembled Ti3C2T /bacterial cellulose composite films with multifunctional electromagnetic shielding and photothermal conversion performances - Hao Liu; Zhou Cui; Lijin Luo; Qiugang Liao; Rui Xiong; Chao Xu; Cuilian Wen; Baisheng Sa (Chemical Engineering Journal, 2023)

Breakage-resistant hydrogel electrode enables ultrahigh mechanical reliability for triboelectric nanogenerators - Rui Li; Zhenyu Xu; Long Li; Junjie Wei; Wenqin Wang; Zejun Yan; Tao Chen (Chemical Engineering Journal, 2023)

Ice template-assisting activation strategy to prepare biomass-derived porous carbon cages for high-performance Zn-ion hybrid supercapacitors - Beichen Xue; Jiahuan Xu; Rui Xiao (Chemical Engineering Journal, 2023)

Friction induced mechanochemistry: self-adaptive lubrication through in-situ tribo-click system - Rui Dong; Yunlei Zhang; Hao-Zhe Xu; Luyao Bao; Shuanhong Ma; Xin-Gang Wang; Qiangliang Yu; Meirong Cai; Feng Zhou; Weimin Liu (Chemical Engineering Journal, 2023)

Z- scheme heterojunction of BiOI nanosheets grown in situ on NH2-UiO-66 crystals with rapid degradation of BPA in real water - Rui Ji; Zhuzhu Zhang; Lechen Tian; Liujun Jin; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2023)

Long-term exposure to ambient particulate matter and kidney function in older adults - Yingxin Li; Xueli Yuan; Jing Wei; Yuanying Sun; Wenqing Ni; Hongmin Zhang; Yan Zhang; Rui Wang; Ruijun Xu; Gongbo Chen; Yuewei Liu; Jian Xu (Atmospheric Environment, 2023)

Effects of Acidification on the Wettability Modification of Coal and Adsorption Characteristics of Coalbed Methane - Rui Zhang; Mei Yuan; Bobo Li; Zhaoping Li; Qing Lv; Shiqing Xu (Natural Resources Research, 2023)

Electroacupuncture promotes remyelination and alleviates cognitive deficit via promoting OPC differentiation in a rat model of subarachnoid hemorrhage - Yingwen Wang; Xiaomin Yang; Yunchuan Cao; Xiaoguo Li; Rui Xu; Jin Yan; Zongduo Guo; Shanquan Sun; Xiaochuan Sun; Yue Wu (Metabolic Brain Disease, 2023)

Investigation of lake shrinkage attributed to climate change over the past 33 years in Inner Mongolia, China - Yanfei Zhang; Zilong Liao; Xiaomin Xu; Wentao Liang; Zhenhua Han; Gang Ji; Rui Jiao (Climatic Change, 2023)

Spatio-temporal variation prediction on Cd content in the rice grains from Northern Zhejiang Plain during 2014–2019 based on high-precision soil geochemical data - Hanqin Yin; Xinzhe Lu; Rui Sun; Chunlei Huang; Zhanjun Kang; Mingxing Xu; Yingchun Wei; ZiHua Cai (Journal of Geographical Sciences, 2023)

Effects of bepridil on early cardiac development of zebrafish - Ya-Lan Wei; Yu-Qing Lei; Zhou-Jie Ye; Xu-Dong Zhuang; Li-Ping Zhu; Xin-Rui Wang; Hua Cao (Cell and Tissue Research, 2023)

Native soil labile organic matter influences soil priming effects - Jing Zhou; Na Qiao; Tongbin Zhu; Rui Pang; Yu Sun; Xiaoqi Zhou; Xingliang Xu (Applied Soil Ecology, 2023)

Effects of earthworm (Eisenia fetida) and arbuscular mycorrhizal fungi improving plant hormones and antioxidant enzymes under simulated acid rain stress - Wang Binglei; Wang Chong; Liu Xuelian; Xue Rui; Liu Mengli; Xu Guangxia; Li Zhiyi (Applied Soil Ecology, 2023)

A combined surface-enhanced Raman spectroscopy (SERS)/colorimetric approach for the sensitive detection of malondialdehyde in biological samples - Xiaojun Luo; Shutong Zhang; Zhichao Xia; Rui Tan; Qiuju Li; Ling Qiao; Yi He; Guoqi Zhang; Zhihong Xu (Analytica Chimica Acta, 2023)

Effects of single or conjoint administration of lactic acid bacteria as potential probiotics on the growth, immune responses, and disease resistance of Carassius auratus - Ruoming Li; Teng Chi; Qing Xu; Juntong Liu; Xiaofeng Shan; Rui Zhou; Jiayun Yao; Wuwen Sun; Guiqin Wang (Aquaculture International, 2023)

Kingella pumchi sp. nov., an organism isolated from human vertebral puncture tissue - Meng Xiao; Ruina Liu; Juan Du; Rui Liu; Lei Zhai; He Wang; Su Yao; Ying-Chun Xu (Antonie van Leeuwenhoek, 2023)

First report of Cytospora tritici causing branch canker on English walnut in China - Shasha Xu; Rui Zhang; Deying Sun; Tiansheng Zhu; Xiaowei Chen; Xiaofei Chen; Xiaofei Chen (Journal of Plant Pathology, 2023)

Sedimentation of cohesive sediments at the subtidal flat affected by wind wave in high turbidity estuary - Qi Shen; Qin Zhu; Shuguang Liu; Sha Lou; Hualin Wu; Zhenchang Zhu; Bin Xu; Rui Yuan (Frontiers in Marine Science, 2023)
Sedimentation is an important mechanism to mitigate the shrinking of tidal flat and to restore its ecological function by means of sand or mud nourishment. To explore the sedimentation of cohesive sediments, a seabed tripod observation system was deployed at the subtidal region of the Hengsha Shoal adjacent to the turbidity maximum zone of the Yangtze Estuary for 11 days. The results showed that the fine sediment with the median grain size around 8 mm occupied the whole water column. The seabed was in relative equilibrium state with the fluctuation of bed level smaller than 16 mm during the moderate wind condition while the seabed experienced a rapid erosion of 38mm and a successive intensive accretion of 68mm during the process of wind wave and swell. The bottom hydrodynamic at 0.3mab during the bed accretion was stronger than that during the bed erosion. The deposition process of cohesive sediments can be better described by the simultaneous deposition paradigm than that by the exclusive deposition paradigm according to the direct data-model comparison of the bed level changes, especially during the impact of fluid mud. Three possible reasons for the better performance of the simultaneous deposition paradigm were proposed. The first possibility is that the fine suspended sediments do maintain a continuous contact with the sediment bed since the direct bed level changes during our observation period has been well reproduced by the simultaneous deposition paradigm. The second possibility is the SSC-induced turbulence damping which facilitates the fine sediment settling in the form of cohesive sediment flocs, indicating the settling of sediments can’t be judged by the critical shear stress for deposition just based on the single particle grain size. The last possibility is the fluid mud-induced overestimated bed shear stress by using turbulent velocity fluctuation above the fluid mud-water interface, which produces excess sediment erosion waiting to be compensated by the simultaneous deposition paradigm. For practical modeling purposes, modeling under the simultaneous deposition paradigm can give satisfactory results for the sedimentation of cohesive sediment especially during the impact of wave or swell.

Effects of chemical additives and mature compost on reducing nitrogen loss during food waste composting - Shangao Xiong; Yongdi Liu; Hao Zhang; Shaoqi Xu; Songrong Li; Xinqi Fan; Rui Chen; Guochun Ding; Ji Li; Yuquan Wei (Environmental Science and Pollution Research, 2023)

Bicarbonate enhanced heterogeneous activation of peroxymonosulfate by copper ferrite nanoparticles for the efficient degradation of refractory organic contaminants in water - Chun Cai; Yangfan Liu; Rui Xu; Jiaheng Zhou; Jin Zhang; Yu Chen; Lingyu Liu; Lexiang Zhang; Shuping Kang; Xianjun Xie (Chemosphere, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Wastewater treatment by anodic oxidation in electrochemical advanced oxidation process: Advance in mechanism, direct and indirect oxidation detection methods - Rui Fu; Peng-Shuang Zhang; Yuan-Xing Jiang; Lin Sun; Xu-Hui Sun (Chemosphere, 2023)

The pretreatment effects of various target pollutant in real coal gasification gray water by coupling pulse electrocoagulation with chemical precipitation methods - Bai-Hong An; Da-Mao Xu; Rui Geng; Yan Cheng; Rui-Bo Qian; Xian-Chun Tang; Zhi-Qiang Fan; Hong-Bin Chen (Chemosphere, 2023)

Interplay of higher plants with lithium pollution: Global trends, meta-analysis, and perspectives - Noman Shakoor; Muhammad Adeel; Imran Azeem; Muhammad Arslan Ahmad; Muhammad Zain; Aown Abbas; Muzammil Hussain; Yaqi Jiang; Pingfan Zhou; Yuanbo Li; Ming Xu; Yukui Rui (Chemosphere, 2023)

Repurposing of spent lithium-ion battery separator as a green reductant for efficiently refining the cathode metals - Wei Hou; Xuanrui Huang; Rui Tang; Yulin Min; Qunjie Xu; Zhenhu Hu; Penghui Shi (Waste Management, 2023)

Insight into the formation and biological effects of natural organic matter corona on silver nanoparticles in water environment using biased cyclical electrical field-flow fractionation - Zhiqiang Tan; Weichen Zhao; Yongguang Yin; Ming Xu; Wenxiao Pan; Yanwanjing Liu; Qinghua Zhang; Bruce K. Gale; Yukui Rui; Jingfu Liu (Water Research, 2023)

Bioaccessibility and bioavailability evaluation of heavy metal(loid)s in ginger in vitro: Relevance to human health risk assessment - Xin Xu; Jinhang Wang; Huihui Wu; Rui Lu; Jun Cui (Science of The Total Environment, 2023)

Hotspots of riverine greenhouse gas (CH4, CO2, N2O) emissions from Qinghai Lake Basin on the northeast Tibetan Plateau - Penglin Lin; Zhiheng Du; Lei Wang; Jingfeng Liu; Qian Xu; Jia Du; Rui Jiang (Science of The Total Environment, 2023)

Contamination vertical distribution and key factors identification of metal(loid)s in site soil from an abandoned Pb/Zn smelter using machine learning - Zhaohui Guo; Yunxia Zhang; Rui Xu; Huimin Xie; Xiyuan Xiao; Chi Peng (Science of The Total Environment, 2023)

Identification of microplastics in human placenta using laser direct infrared spectroscopy - Long Zhu; Jingying Zhu; Rui Zuo; Qiujin Xu; Yanhua Qian; Lihui AN (Science of The Total Environment, 2023)

High ambient temperatures are associated with urban crime risk in Chicago - Kun Hou; Liqiang Zhang; Xia Xu; Feng Yang; Baozhang Chen; Wei Hu; Rui Shu (Science of The Total Environment, 2023)

Synergistic activation of anionic redox via cosubstitution to construct high-capacity layered oxide cathode materials for sodium-ion batteries - Haocheng Ji; Wenhai Ji; Haoyu Xue; Guojie Chen; Rui Qi; Zhongyuan Huang; Hui Fang; Mihai Chu; Lele Liu; Zhewen Ma; Shenyang Xu; Jingjun Zhai; et al. (Science Bulletin, 2023)

OsHLS1 regulates plant height and development by controlling active gibberellin accumulation in rice (Oryza sativa L.) - Tonghua Zhang; Jiafu Wang; Rui Luo; Jianmin Man; Qing Long; Ning Xu (Plant Science, 2023)

Electrochemical behavior of gold dissolution with a novel eco-friendly synthetic gold lixiviant - Qian Li; Siyu Dong; Yan Zhang; Rui Xu; Yongbin Yang; Tao Jiang (Minerals Engineering, 2023)

Characteristics and origin of Lower Triassic Feixianguan Formation dolostones on the west side of Kaijiang–Liangping Trough, northeastern Sichuan Basin, China - Ling Zhou; Guangwei Wang; Ya Zhang; Yanping Qiao; Fang Hao; Rui Xu; Li Quan; Ping Wang (Marine and Petroleum Geology, 2023)

Selective detection of trace carbon monoxide at room temperature based on CuO nanosheets exposed to (111) crystal facets - Yuanyuan Wu; Ji Li; Mingsong Lv; Xianfa Zhang; Rui Gao; Chuanyu Guo; Xiaoli Cheng; Xin Zhou; Yingming Xu; Shan Gao; Zoltán Major; Lihua Huo (Journal of Hazardous Materials, 2023)

Environment relevant concentrations of lithium influence soybean development via metabolic reprogramming - Noman Shakoor; Muhammad Adeel; Muhammad Arslan Ahmad; Muzammil Hussain; Imran Azeem; Muhammad Zain; Pingfan Zhou; Yuanbo Li; Ming Xu; Yukui Rui (Journal of Hazardous Materials, 2023)

Impact of international trade on water scarcity: An assessment by improving the Falkenmark indicator - Rui Zhong; Aifang Chen; Dandan Zhao; Ganquan Mao; Xu Zhao; Hao Huang; Junguo Liu (Journal of Cleaner Production, 2023)

Pollution characteristics and health risk assessment of polycyclic aromatic hydrocarbons and nitrated polycyclic aromatic hydrocarbons during heating season in Beijing - Xurong Bai; Jie Wei; Yanqin Ren; Rui Gao; Fahe Chai; Hong Li; Fei Xu; Yuxue Kong (Journal of Environmental Sciences, 2023)

Synthesis and influencing factors of high-performance concrete based on copper tailings for efficient solidification of heavy metals - Ruosong Xie; Rui Ge; Zhishuncheng Li; Guangfei Qu; Yingjie Zhang; Youxiao Xu; Yingda Zeng; Ziying Li (Journal of Environmental Management, 2023)

Starting up anammox system with high efficiency nitrogen removal at low temperatures: Performance optimization, sludge characterization and microbial community analysis - Liurui Peng; Rui Shi; Youqi Tao; Qian Huang; Maoyuan Yang; Yuecheng He; Wenlai Xu (Journal of Environmental Management, 2023)

Formation mechanism of typical aromatic sulfuric anhydrides and their potential role in atmospheric nucleation process - Haijie Zhang; Rui Gao; Hong Li; Yunfeng Li; Yisheng Xu; Fahe Chai (Journal of Environmental Sciences, 2023)

Habitat quality dynamics in China's first group of national parks in recent four decades: Evidence from land use and land cover changes - Xin Chen; Le Yu; Yue Cao; Yidi Xu; Zhicong Zhao; Youbo Zhuang; Xuehua Liu; Zhenrong Du; Tao Liu; Bo Yang; Lu He; Hui Wu; et al. (Journal of Environmental Management, 2023)

Learn then match: A fast coarse-to-fine depth image-based indoor localization framework for dark environments via deep learning and keypoint-based geometry alignment - Qing Li; Rui Cao; Jiasong Zhu; Hao Fu; Baoding Zhou; Xu Fang; Sen Jia; Shenman Zhang; Kanglin Liu; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Conformation changes and emulsifying properties of myofibrillar proteins in water: Effects of electrostatic interaction with chitosan - Mingyuan Huang; Yujuan Xu; Lina Xu; Yun Bai; Xianming Zeng; Rui Zheng; Xinglian Xu (Food Research International, 2023)

Combination of pulsed electric field and pH shifting improves the solubility, emulsifying, foaming of commercial soy protein isolate - Rui Wang; Lang-Hong Wang; Qing-Hui Wen; Fei He; Fei-Yue Xu; Bo-Ru Chen; Xin-An Zeng (Food Hydrocolloids, 2023)

New insights into the regulation mechanism of red claw crayfish (Cherax quadricarinatus) hepatopancreas under air exposure using transcriptome analysis - Yao-Peng Lu; Pei-Hua Zheng; Xiu-Xia Zhang; Jun-Tao Li; Ze-Long Zhang; Jia-Rui Xu; Yong-Qi Meng; Jia-Jun Li; Jian-An Xian; An-Li Wang (Fish & Shellfish Immunology, 2023)

Composite organic amendment boosts soil remediation and Cd detoxification to rape under different nitrogen level - Xu Zhang; Qingkai Guan; Linghui Kong; Rui Yang; Xuesheng Liu; Juanjuan Qu; Yu Jin (European Journal of Soil Biology, 2023)

Controlled design of Na–P1 zeolite/ porous carbon composites from coal gasification fine slag for high-performance adsorbent - Rui Shu; Qixia Qiao; Feiqiang Guo; Kaiming Dong; Sha Liu; Liya Xu; Yonghui Bai; Nan Zhou (Environmental Research, 2023)

Maternal atmospheric particulate matter exposure and risk of adverse pregnancy outcomes: A meta-analysis of cohort studies - Liangliang Ju; Lei Hua; Hanbing Xu; Changlian Li; Shu Sun; Qi Zhang; Jiyu Cao; Rui Ding (Environmental Pollution, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Mechanism of excavation-induced cracking of the protective layer of a rock bench in a large underground powerhouse under high tectonic stress - Yuelin Xia; Xia-Ting Feng; Chengxiang Yang; Shaojun Li; Dingping Xu; Quan Jiang; Rui Kong; Yonghong Li; Zhiguo Li (Engineering Geology, 2023)

Permanent displacement reliability analysis of soil slopes subjected to mainshock-aftershock sequences - Gan Wang; Rui Pang; Xiang Yu; Bin Xu (Computers and Geotechnics, 2023)

Metabolomics analysis reveals the response mechanism to carbonate alkalinity toxicity in the gills of Eriocheir sinensis - Rui Zhang; Zhigang Zhao; Mingshuai Li; Liang Luo; Shihui Wang; Kun Guo; Wei Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Combining a novel biofilm reactor with a constructed wetland for rural, decentralized wastewater treatment - Rui Zhang; Xianchang Liu; Lutian Wang; Pan Xu; Kai Li; Xiaoxiao Chen; Rong Meng; Yuewu Pu; Xuetong Yang; Diederik P.L. Rousseau; Stijn W.H. Van Hulle (Chemical Engineering Journal, 2023)

Patternable thermal conductive interface materials enabled by vitrimeric phase change materials - Li-Mei Peng; Zhao Xu; Jie Yang; Lu Bai; Rui-Ying Bao; Ming-Bo Yang; Wei Yang (Chemical Engineering Journal, 2023)

Coexistence of microplastics alters the inhibitory effect of antibiotics on sludge anaerobic digestion - Yinping Xiang; Weiping Xiong; Zhaohui Yang; Rui Xu; Yanru Zhang; Mengru Wu; Yuhang Ye; Haihao Peng; Jing Tong; Dongbo Wang (Chemical Engineering Journal, 2023)

One-dimensional copper bromide based inorganic-organic hybrids as fuels for hypergolic bipropellants with hydrogen peroxide as oxidizer - Ya-Jie Wang; Xu-Yang Wang; Hong Xu; Wei-Wei Ren; Rui Pang; Li Yang; Wen-Chao Tong; Qian-You Wang; Shuang-Quan Zang (Chemical Engineering Journal, 2023)

Multifunctional lysosome-targetable fluorescent probe for imaging peroxynitrite in acute liver injury model - Kai Wang; Rui Guo; Xu-Yang Chen; Yu-Shun Yang; Lu-Qin Qiao; Ming-Lin Wang (Chemical Engineering Journal, 2023)

Robust emission in near-infrared II of lanthanide nanoprobes conjugated with Au (LNPs-Au) for temperature sensing and controlled photothermal therapy - Guofeng Liu; Zhenxing Wang; Wan Sun; Xiaohui Lin; Rui Wang; Chonghui Li; Li Zong; Zuoling Fu; Hanping Liu; Shicai Xu (Chemical Engineering Journal, 2023)

In-situ growth of bimetallic FeCo-MOF on magnetic biochar for enhanced clearance of tetracycline and fruit preservation - Yi-Cai Jiang; Meng-Fan Luo; Zi-Nuo Niu; Si-Yuan Xu; Yue Gao; Yuan Gao; Wen-Juan Gao; Jing-Jing Luo; Rui-Lin Liu (Chemical Engineering Journal, 2023)

Enhancing structural and cycle stability of Prussian blue cathode materials for calcium-ion batteries by introducing divalent Fe - Chong-Yu Du; Zi-Hao Zhang; Xun-Lu Li; Rui-Jie Luo; Cui Ma; Jian Bao; Jie Zeng; Xuan Xu; Fei Wang; Yong-Ning Zhou (Chemical Engineering Journal, 2023)

Lattice doping of Zn boosts oxygen vacancies in Co3O4 Nanocages: Improving persulfate activation via forming Surface-Activated complex - Mei-Mei Wang; Li-Juan Liu; Jia-Rui Xi; Ying Ding; Peng-Xi Liu; Liang Mao; Bing-Jie Ni; Wei-Kang Wang; Juan Xu (Chemical Engineering Journal, 2023)

Boosting elementary steps kinetics towards energetic alkaline hydrogen evolution via dual sites on phase-separated Ni–Cu–Mn/hydroxide - Zhimin Li; Sisi Xin; Yirong Zhang; Zhengfu Zhang; Chengping Li; Caiju Li; Rui Bao; Jianhong Yi; Mingli Xu; Jinsong Wang (Chemical Engineering Journal, 2023)

Preparation and characterization of bioplastics from silylated cassava starch and epoxidized soybean oils - Jianlei Yang; Shicai Xu; Wenqing Wang; Xiuzhen Ran; Yern Chee Ching; Xiao Sui; Yunwei Wei; Rui Wang; Naif Mohammed Al-Hada (Carbohydrate Polymers, 2023)

Experimental investigation into the boundary layer structure near the tip of a dam-break wave on a dry, rough and horizontal bed - Beibei Xu; Rui Shi; Peter Nielsen; Zheng Gong (Coastal Engineering, 2023)

Plant-associated Microbe System in Treatment of Heavy Metals–contaminated Soil: Mechanisms and Applications - Zhiming Ren; Rui Cheng; Peng Chen; Yuanyuan Xue; Hong Xu; Yao Yin; Guangtuan Huang; Wei Zhang; Lehua Zhang (Water, Air, & Soil Pollution, 2023)

Positional cloning identified HvTUBULIN8 as the candidate gene for round lateral spikelet (RLS) in barley (Hordeum vulgare L.) - Dandan Qin; Gang Liu; Rui Liu; Chunchao Wang; Fuchao Xu; Qing Xu; Yu Ling; Guoqing Dong; Yanchun Peng; Shuangtao Ge; Ganggang Guo; Jing Dong; et al. (Theoretical and Applied Genetics, 2023)
Key message Map-based cloning, subcellular localization, virus-induced-gene-silencing and transcriptomic analysis reveal HvTUB8 as a candidate gene with pleiotropic effects on barley spike and leaf development via ethylene and chlorophyll metabolism. Abstract Barley lateral spikelet morphology and grain shape play key roles in grain physical quality and yield. Several genes and QTLs for these traits have been cloned or fine mapped previously. Here, we report the phenotypic and genotypic analysis of a barley mutant with round lateral spikelet (rls) from cv. Edamai 934. rls had round lateral spikelet, short but round grain, shortened awn, thick glume and dark green leaves. Histocytologic and ultrastructural analysis revealed that the difference of grain shape of rls was caused by change of cell arrangement in glume, and the dark leaf color resulted from enlarged chloroplast. HvTUBULIN8 ( HvTUB8 ) was identified as the candidate gene for rls by combination of RNA-Seq, map-based-cloning, virus-induced-gene-silencing (VIGS) and protein subcellular location. A single G-A substitution at the third exon of HvTUB8 resulted in change of Cysteine 354 to tyrosine. Furthermore, the mutant isoform Hvtub8 could be detected in both nucleus and cytoplasm, whereas the wild-type protein was only in cytoplasm and granular organelles of wheat protoplasts. Being consistent with the rare phenotype, the “A” allele of HvTUB8 was only detected in rls , but not in a worldwide barley germplasm panel with 400 accessions. VIGS confirmed that HvTUB8 was essential to maintain spike integrity. RNA-Seq results suggested that HvTUB8 may control spike morphogenesis via ethylene homeostasis and signaling, and control leaf color through chlorophyll metabolism. Collectively, our results support HvTUB8 as a candidate gene for barley spike and leaf morphology and provide insight of a novel mechanism of it in barley development.

Expression of phenylalanine ammonia lyase as an intracellularly free and extracellularly cell surface-immobilized enzyme on a gut microbe as a live biotherapeutic for phenylketonuria - Yu Jiang; Bingbing Sun; Fenghui Qian; Feng Dong; Chongmao Xu; Wuling Zhong; Rui Huang; Qiwei Zhai; Yu Jiang; Sheng Yang (Science China Life Sciences, 2023)

Clinical Decision on Disorders of Consciousness After Acquired Brain Injury: Stepping Forward - Rui-Zhe Zheng; Zeng-Xin Qi; Zhe Wang; Ze-Yu Xu; Xue-Hai Wu; Ying Mao (Neuroscience Bulletin, 2023)

LncRNA as potential biomarker and therapeutic target in glioma - Xun Xu; Yuan Liang; Ilgiz Gareev; Yanchao Liang; Rui Liu; Ning Wang; Guang Yang (Molecular Biology Reports, 2023)

The draft genome sequence and characterization of Exserohilum rostratum, a new causal agent of maize leaf spot disease in Chinese Mainland - Qingzhou Ma; Chongyang Cheng; Yuehua Geng; Rui Zang; Yashuang Guo; Lixin Yan; Chao Xu; Meng Zhang; Haiyan Wu (European Journal of Plant Pathology, 2023)

Leaching and characterization studies of heavy metals in contaminated soil using sequenced reagents of oxalic acid, citric acid, and a copolymer of maleic and acrylic acid instead of ethylenediaminetetraacetic acid - Eric Tindanzor; Zhaohui Guo; Tianshuang Li; Rui Xu; Xiyuan Xiao; Chi Peng (Environmental Science and Pollution Research, 2023)

Correction to: Characterization of keystone taxa and microbial metabolic potentials in copper tailing soils - Qiao Fan; Yeqiang Chen; Rui Xu; Zhaohui Guo (Environmental Science and Pollution Research, 2023)

China’s carbon dioxide emission forecast based on improved marine predator algorithm and multi-kernel support vector regression - Xiwen Qin; Siqi Zhang; Xiaogang Dong; Yichang Zhan; Rui Wang; Dingxin Xu (Environmental Science and Pollution Research, 2023)

Application of chelate GLDA for remediating Cd-contaminated farmlands using Tagetes patula L. - Hongchuan Li; Rui Jin; Zhaowen Xu; Hongxiang Hu; Yusef Kianpoor Kalkhajeh; Yingying Zhao; Linchuan Zhan (Environmental Science and Pollution Research, 2023)

The impact of natural disasters on household debt: evidence from 2014 China family panel studies - Rui Zhang; Sheng Xu; Ruidong Sun (Environmental Science and Pollution Research, 2023)

Characterization of keystone taxa and microbial metabolic potentials in copper tailing soils - Qiao Fan; Yeqiang Chen; Rui Xu; Zhaohui Guo (Environmental Science and Pollution Research, 2023)

Selenite Ameliorates Cadmium-induced Cytotoxicity Through Downregulation of ROS Levels and Upregulation of Selenoprotein Thioredoxin Reductase 1 in SH-SY5Y Cells - Hecheng Wang; Shibo Sun; Yan Ren; Rui Yang; Jianli Guo; Yu Zong; Qiuxian Zhang; Jing Zhao; Wei Zhang; Weiping Xu; Shui Guan; Jianqiang Xu (Biological Trace Element Research, 2023)

Crosstalk between exosomes and autophagy in spinal cord injury: fresh positive target for therapeutic application - Rui-yu Li; Qi Hu; Xu Shi; Zhen-yu Luo; Dong-hua Shao (Cell and Tissue Research, 2023)
Spinal cord injury (SCI) is a very serious clinical traumatic illness with a very high disability rate. It not only causes serious functional disorders below the injured segment, but also causes unimaginable economic burden to social development. Exosomes are nano-sized cellular communication carriers that exist stably in almost all organisms and cell types. Because of their capacity to transport proteins, lipids, and nucleic acids, they affect various physiological and pathological functions of recipient cells and parental cells. Autophagy is a process that relies on the lysosomal pathway to degrade cytoplasmic proteins and organelles and involves a variety of pathophysiological processes. Exosomes and autophagy play critical roles in cellular homeostasis following spinal cord injury. Presently, the coordination mechanism of exosomes and autophagy has attracted much attention in the early efficacy of spinal cord injury. In this review, we discussed the interaction of autophagy and exosomes from the perspective of molecular mechanisms, which might provide novel insights for the early therapeutic application of spinal cord injury.

Influence mechanism of the non-uniform inflow on performance of reactor coolant pump - Yu Song; Song Huang; Rui Xu; Zhengchuan Zhang; Junlian Yin; Dezhong Wang (Annals of Nuclear Energy, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)